Hollow silica sol containing monovalent alkali metal ions and method for producing the same

JP7939623B2Active Publication Date: 2026-10-22NISSAN CHEM CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2025071885
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-07-28
Filing Date
2025-04-23
Publication Date
2026-10-22
Estimated Expiration
2044-07-26

AI Technical Summary

Benefits of technology

【0008】 中空シリカ粒子を含む分散体(中空シリカゾル)は安定性を有する事で中空シリカ粒子の凝集がなく、中空シリカ粒子径の変化が少ない中空シリカゾルが得られる。安定性の高い中空シリカゾルは被覆膜とした時に、粒子径の変化が少ないため被覆膜表面の凹凸の低減や、透明性の向上が達成される。 中空シリカゾル中のアルカリ金属イオン(例えばナトリウムイオン)は一定範囲であることが好ましく、多すぎる場合にはアルカリ金属イオンの被覆膜からの溶出や被覆膜の電気絶縁性に問題を生じることがある。また、少なすぎる場合には、中空シリカ粒子は外殻の内部が空洞になっていて中空シリカ粒子自体の比重が中実シリカ粒子よりも低いため粒子の反発力が低い場合は、粒子が集まりやすく凝集しやすい傾向があり、その場合は粒子反発力を高めるために一定量のアルカリ金属イオン(例えばナトリウムイオン)が必要になる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007939623000001
    Figure 0007939623000001
  • Figure 0007939623000002
    Figure 0007939623000002
  • Figure 0007939623000003
    Figure 0007939623000003
Patent Text Reader

Abstract

To provide: hydrosol and organic solvent sol including a highly stable hollow silica particle; and a method for increasing stability of the sol having decreased storage stability and a production method thereof.SOLUTION: Hollow silica sol includes: a hollow silica particle having a space enclosed by a shell; and a monovalent alkali metal ion. The monovalent alkali metal ion is included in the sol at a ratio of a molar number thereof in terms of M2O (where M represents a monovalent alkali metal atom) to a molar number of SiO2 of the hollow silica particle of 7.12×10-6 to 285×10-6. In the sol, an average particle diameter determined by dynamic light scattering after storage at 50°C for 48 hours is in a range of at most 2.0 times the average particle diameter determined by the dynamic light scattering before the storage. The average particle diameter determined by the dynamic light scattering is 20 to 150 nm. In a stabilization method, the monovalent alkali metal ion is added to the hollow silica sol having a value of a particle diameter determined by the dynamic light scattering increased compared with that in production at the ratio described above relative to the SiO2 of the hollow silica particle in the hollow silica sol to decrease the increased value of the particle diameter determined by the dynamic light scattering.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a sol in which hollow silica particles containing monovalent alkali metal ions such as sodium ions are dispersed in water or an organic solvent, a method for producing the same, and a film-forming composition. [Background technology]

[0002] Hollow silica particles, which have a silica outer shell and a space inside the outer shell, possess properties such as low refractive index, low thermal conductivity (thermal insulation), and electrical insulation due to their characteristics. Hollow silica particles consist of a core corresponding to a cavity and an outer shell that forms the outside of the core. An aqueous dispersion of hollow silica particles can be obtained by forming a silica layer on the outside of the core in an aqueous medium and then removing the core. The average particle size is in the range of 5 to 500 nm, the refractive index is in the range of 1.15 to 1.38, silica is represented by SiO2, and inorganic oxides other than silica are represented by MO X The molar ratio MO when expressed as X A silica-based fine particle having a cavity inside its outer shell is disclosed, characterized in that the / SiO2 is in the range of 0.0001 to 0.2 and the alkali metal oxide content is 5 ppm or less as A2O (A: alkali metal element) (see Patent Document 1).

[0003] A silica-based fine particle is disclosed, having a porous material and / or cavities inside its outer shell layer, wherein the ratio of the specific surface area (SB) of the fine particle measured by the BET method to the specific surface area (SC) expressed by the following formula (SB / SC) is in the range of 1.1 to 5, the refractive index is in the range of 1.15 to 1.38, the alkali metal oxide content is 5 ppm or less as M2O (M: alkali metal element) per silica-based fine particle, and the ammonia and / or ammonium ion content is 1500 ppm or less as NH3 per silica-based fine particle (see Patent Document 2). SC(m 2 / g) = 6000 / Dp(nm)·ρ (However, Dp is the average particle size (nm) of silica-based fine particles, and ρ is the density (g / ml).) [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2011-046606 [Patent Document 2] Japanese Patent Publication No. 2013-121911 [Overview of the project] [Problems that the invention aims to solve]

[0005] The present invention relates to aqueous sols and organic solvent sols containing highly stable hollow silica particles, and further to a method for improving the stability of the above sols whose storage stability has deteriorated, and a method for producing the same. [Means for solving the problem]

[0006] In its first aspect, the present invention comprises hollow silica particles having a space inside the outer shell and monovalent alkali metal ions, wherein the number of moles of the monovalent alkali metal ions converted to M2O (where M represents a monovalent alkali metal atom) is 7.12 × 10⁻⁶ relative to the number of moles of SiO2 in the hollow silica particles. -6 ~285×10 -6 A hollow silica sol containing in a certain proportion, wherein the average particle size measured by dynamic light scattering after storing the sol at 50°C for 48 hours is within 2.0 times the average particle size measured by dynamic light scattering before storage. Alternatively, hollow silica particles with a space inside the outer shell, and monovalent alkali metal ions relative to the SiO2 of the hollow silica particles in a molar ratio converted to M2O (where M is a monovalent alkali metal) of 7.12 × 10 -6 ~285×10 -6 A sol containing a certain proportion, wherein the particle size measured by dynamic light scattering after storage at 50°C for 48 hours is within 2.0 times the value before storage. The above hollow silica sol located, From a second perspective, the hollow silica sol described in the first perspective, wherein the monovalent alkali metal ion is a sodium ion. As a third point, the hollow silica sol described in the first or second point, having an average particle diameter of 20 to 150 nm as determined by dynamic light scattering, As a fourth point, the hollow silica sol according to any one of the first to third points, further comprising an amine, wherein the amine is present in an amount of 0.001 to 10% by mass relative to the SiO2 of the hollow silica particles. From a fifth perspective, the hollow silica sol according to the fourth perspective, wherein the amine is at least one amine selected from the group consisting of primary amines, secondary amines, and tertiary amines having 1 to 10 carbon atoms. As a sixth point of view, the above amine is a water-soluble amine with a water solubility of 80 g / L or more, a hollow silica sol as described in the fourth or fifth point of view, As a seventh viewpoint, the hollow silica sol described in any one of the first to sixth viewpoints further contains aluminum atoms forming aluminosilicate sites, the aluminum atoms are bonded to the surface of the hollow silica particles, the mass of the aluminum atoms is in the range of 100 to 20,000 ppm (A) in terms of Al2O3 relative to the mass of SiO2 of the hollow silica particles, and the mass of the aluminum atoms is measured by the leaching method. Alternatively, the hollow silica sol according to any one of the first to sixth aspects, wherein the hollow silica particles further contain aluminum atoms forming aluminosilicate sites, and the aluminum atoms, as measured by the leaching method, are bonded to the surface of the hollow silica particles at a ratio of 100 to 20000 ppm / SiO2 (A) in terms of Al2O3 equivalent to SiO2 in the hollow silica particles. As an eighth viewpoint, the leaching method measurement described above uses an aqueous solution of at least one mineral acid selected from the group consisting of sulfuric acid, nitric acid, and hydrochloric acid, to leach aluminum atoms from a compound containing aluminum atoms bonded to the surface of hollow silica particles, as described in the seventh viewpoint. Alternatively, the leaching method measurement is performed by leaching hollow silica particles with an aqueous solution of at least one mineral acid selected from the group consisting of sulfuric acid, nitric acid, and hydrochloric acid, and the compound containing aluminum atoms bonded to the surface of the hollow silica particles is expressed as the ratio (A) of SiO2 of the hollow silica particles to 1 g in terms of Al2O3, as described in the seventh aspect, As a ninth point, the hollow silica sol described in the seventh or eighth point, wherein the mass of aluminum atoms present in the entire hollow silica particles is expressed as a ratio (B) of 120 to 50,000 ppm relative to the mass of SiO2 in the hollow silica particles, calculated in terms of Al2O3, and the mass of aluminum atoms is measured by dissolving the hollow silica particles in an aqueous hydrofluoric acid solution, and the ratio (A) / ratio (B) is 0.002 to 1.0. Alternatively, the hollow silica sol described in the 7th or 8th perspective, wherein the aluminum atoms present throughout the hollow silica particles, measured by dissolving the hollow silica particles in an aqueous hydrofluoric acid solution, are bonded at a ratio of 120 to 50,000 ppm / SiO2 (B) in terms of Al2O3, and the above (A) / (B) is 0.001 to 1.0. As the tenth point of view, a hollow silica sol described in any one of the first to ninth points of view, including the hollow silica particles described above, wherein the ratio of [specific surface area of ​​silica particles by the BET method (nitrogen gas adsorption method) (C)] / [specific surface area of ​​silica particles calculated from a transmission electron microscope (D)] is 1.40 to 5.00,

[0007] As the eleventh viewpoint, a hollow silica sol according to any one of the first to tenth viewpoints, comprising hollow silica particles having a surface charge amount of 5 to 250 μeq / g per gram in terms of SiO2, Alternatively, the hollow silica particles described in any one of the first to tenth views, which include hollow silica particles in which the surface charge amount per gram of SiO2 is 5 to 250 μeq / g. Silica sol, From the twelfth perspective, the above hollow silica particles are further expressed by the following formulas (1) and (2): [ka] (In formula (1), R 1 is a group bonded to a silicon atom, and independently of each other, represents an alkyl group, a halogenated alkyl group, an alkenyl group, or an aryl group, or represents an organic group having an epoxy group, a (meth)acryloyl group, a mercapto group, an amino group, a ureido group, a polyether group, a carboxy group, a protected carboxy group, a carboxy group-generating group, an imide group, or a cyano group and bonded to the silicon atom via a Si-C bond, or represents a combination of these groups, R 2 is a group or atom bonded to a silicon atom, and independently of each other, represents an alkoxy group having 1 or more carbon atoms, an acyloxy group, a hydroxy group, or a halogen atom, or represents a combination of these groups, a represents an integer of 1 to 3, In formula (2), R 3 is a group bonded to a silicon atom, and independently of each other, represents an alkyl group, a halogenated alkyl group, an alkenyl group, or an aryl group, or represents an organic group having an epoxy group, a (meth)acryloyl group, a mercapto group, an amino group, a ureido group, a polyether group, a carboxy group, a protected carboxy group, a carboxy group-generating group, an imide group, or a cyano group and bonded to the silicon atom via a Si-C bond, or represents a combination of these groups, R 4 is a group or atom bonded to a silicon atom, and independently of each other, represents an alkoxy group having 1 or more carbon atoms, an acyloxy group, a hydroxy group, or a halogen atom, or represents a combination of these groups, Y is a group or atom bonded to a silicon atom, and represents an alkylene group, an NH group, or an oxygen atom, b represents an integer of 1 to 3, and c represents an integer of 0 or 1.) The hollow silica sol according to any one of claims 1 to 11, comprising hollow silica particles coated with at least one silane compound selected from the group consisting of the compounds represented by As a thirteenth aspect, the hollow silica sol according to any one of the first to twelfth aspects, wherein the dispersion medium is water, an alcohol having 1 to 10 carbon atoms, a ketone, an ether, an amide, a urea, or an ester. As the 14th viewpoint, a film-forming composition comprising hollow silica particles derived from any one of the hollow silica sols described in the 1st to 13th viewpoints, and an organic resin or polysiloxane, As the 15th point, a film obtained from the film-forming composition described in the 14th point, having a visible light transmittance of 80% or more, From the 16th perspective, consider the following steps (I) to (II): (I) Step: A step of preparing a hollow silica sol containing a dispersion medium. (II) Step: Add monovalent alkali metal ions to the hollow silica sol from step (I) in a molar ratio of 7.12 × 10¹⁶ to the SiO2 of the hollow silica particles, converted to M₂O (where M represents a monovalent alkali metal atom). -6 ~285×10 -6 A process of adding monovalent alkali metal ions to adjust the ratio. A method for producing hollow silica sol according to any one of the first to thirteenth aspects, including As the 17th point, the method for producing hollow silica sol as described in the 16th point, wherein in step (II), the monovalent alkali metal ion is a sodium ion. The 18th aspect is the method for producing hollow silica sol according to the 17th aspect, wherein the adjustment of the sodium ion content in step (II) above is done by contacting the hollow silica sol obtained in step (I) with a cation exchange resin, or by adding a sodium source. From the 19th perspective, the method for producing hollow silica sol as described in the 17th perspective, wherein the addition of the sodium source in step (II) above is the addition of sodium hydroxide. The 20th aspect is a method for producing a hollow silica sol according to any one of the 16th to 19th aspects, wherein the dispersion medium in steps (I) and (II) above is water, an alcohol having 1 to 10 carbon atoms, a ketone, an ether, an amide, a urea, or an ester. As the 21st viewpoint, a method for producing hollow silica sol according to any one of the 16th to 20th viewpoints, wherein at least one step selected from (i) to (iv) below is added to the above steps (I), (II), or both steps. (i): Adding an amine to a hollow silica sol, (ii) Add sodium aluminate as an aluminum source and heat to form aluminosilicate sites in hollow silica particles. (iii): Replacing the dispersion medium with another dispersion medium. (iv): The hollow silica particles are further coated with at least one silane compound selected from the group consisting of formulas (1) and (2). From the 22nd perspective, a method for stabilizing a hollow silica sol containing hollow silica particles having a space inside the outer shell, In hollow silica sols where the average particle size measured by dynamic light scattering has increased compared to the time of manufacture, The number of moles of the above monovalent alkali metal ions converted to M2O (where M represents a monovalent alkali metal atom) is 7.12 × 10⁻⁶ relative to the number of moles of SiO2 in the hollow silica particles in the hollow silica sol. -6 ~285×10 -6 The monovalent alkali metal ions are added in such a molar ratio as follows: A method for stabilizing a hollow silica sol as described in the first aspect, characterized by reducing the average particle size by the increased dynamic light scattering method. Alternatively, a method for stabilizing a hollow silica sol containing hollow silica particles having a space inside the outer shell, wherein the hollow silica sol having a dynamic light scattering particle diameter value that is increased compared to the dynamic light scattering particle diameter at the time of manufacture, contains monovalent alkali metal ions in a molar ratio converted to M2O (where M is a monovalent alkali metal) relative to the SiO2 of the hollow silica particles in the hollow silica sol. 7.12 × 10 -6 ~285×10 -6 A method for stabilizing a hollow silica sol as described in the first aspect, characterized by adding it in a certain proportion to reduce the increased dynamic light scattering particle size, and The 23rd aspect is a method for stabilizing the hollow silica sol described in the 22nd aspect, wherein the monovalent alkali metal ion is a sodium ion. [Effects of the Invention]

[0008] Dispersions containing hollow silica particles (hollow silica sols) are stable, preventing aggregation of the hollow silica particles and resulting in a hollow silica sol with minimal change in particle size. When a highly stable hollow silica sol is used as a coating film, the minimal change in particle size reduces surface irregularities and improves transparency. The amount of alkali metal ions (e.g., sodium ions) in hollow silica sol is preferably within a certain range. If there are too many, problems may arise with the elution of alkali metal ions from the coating film or with the electrical insulation properties of the coating film. Conversely, if there are too few, hollow silica particles have a hollow interior and a lower specific gravity than solid silica particles, resulting in lower particle repulsion. In such cases, the particles tend to aggregate easily, and a certain amount of alkali metal ions (e.g., sodium ions) is needed to increase the particle repulsion.

[0009] In this invention, stability is improved by combining amine molecules and sodium ions as the alkaline component. This is thought to be because the presence of bulky amine molecules and sodium ions on the particle surface mutually enhances the repulsive force between silica particles. Furthermore, in this invention, silica particles can form aluminosilicate sites by doping aluminum atoms onto their surface, and the presence of an alkali metal counterion for the negatively charged aluminum atoms improves the stabilization of the aluminosilicate sites. [Modes for carrying out the invention]

[0010] This invention comprises hollow silica particles having a space inside the outer shell and monovalent alkali metal ions, with a molar ratio of 7.12 × 10⁻¹⁰ of monovalent alkali metal ions relative to the SiO₂ of the hollow silica particles, converted to M₂O (where M represents a monovalent alkali metal atom). -6~285×10 -6 The hollow silica sol contains in a certain proportion, wherein the value of the particle diameter measured by dynamic light scattering (average particle diameter) after storing the sol at 50°C for 48 hours is within 2.0 times the value of the particle diameter measured by dynamic light scattering before storage. Hollow silica particles have a silica outer shell with a space inside the outer shell. Hollow silica is obtained by forming a silica-based outer shell on the surface of a core-like portion called a template in a dispersion medium, and then removing the core-like portion.

[0011] Hollow silica particles are required to be stably dispersed in a dispersion medium. The presence of silanol groups, organic functional groups, and aluminum atom-doped aluminosilicate sites on the surface of hollow silica particles can be stabilized by adding monovalent alkali metal ions to the surface of the hollow silica particles. Silanol groups, organic functional groups, and aluminosilicate sites have polymerizable functional groups such as hydroxyl groups. The interaction of these polymerizable functional groups can lead to particle instability and an increase in particle size due to weak condensation (entanglement) between particles and crosslinking between particles by hydrogen bonding. However, it is thought that the addition of monovalent alkali metal ions to these polymerizable functional groups changes the morphology of the hydroxyl groups, thereby suppressing the factors that cause instability. These polymerizable functional groups can be destabilized by heating, and the stability of hollow silica sol can be evaluated by checking its stability after 48 hours at 50°C. Examples of monovalent alkali metal ions include lithium ions, sodium ions, potassium ions, rubidium ions, and cesium ions, but lithium ions, sodium ions, and potassium ions are preferred, and sodium ions are particularly preferred.

[0012] The monovalent alkali metal ion content in the dispersion (sol) is 7.12 × 10⁻¹⁰ molar ratio, calculated as M₂O (where M represents a monovalent alkali metal atom) per unit mass of SiO₂ in hollow silica particles. -6 ~285×10 -6 , or 7.12 × 10-6 ~237×10 -6 , or 7.12 × 10 -6 ~190×10 -6 、 or 20 x 10 -6 ~285×10 -6 、 or 50 x 10 -6 ~285×10 -6 It is possible to do so. Furthermore, the amount of monovalent alkali metal ions can be set to an amount equivalent to 15 ppm to 600 ppm, or 15 ppm to 500 ppm, or 15 ppm to 400 ppm, when the molar ratio of monovalent alkali metal ions per mass of SiO2 in hollow silica particles is converted to M2O (where M represents a monovalent alkali metal atom) in the dispersion (sol).

[0013] The hollow silica sol of the present invention can have an average particle diameter measured by dynamic light scattering in the range of 20 to 150 nm. Furthermore, the particle diameter measured by dynamic light scattering after storing the hollow silica sol at 50°C for 48 hours is within 2.0 times, 1.5 times, or 1.1 times compared to before storage. The present invention also includes the possibility that the particle diameter measured by dynamic light scattering after storage at 50°C for 48 hours is smaller than that before storage. Therefore, the lower limit can be set to 0.8 times or more, 0.9 times or more, or 1.0 times or more. In this invention, the stability of the hollow silica sol can be ensured by including sodium ions within the above range. This means that sodium ions can be included within the above range before the sol containing hollow silica particles becomes unstable. Furthermore, by adding the above sodium ions to a sol containing unstable hollow silica particles, the aggregated state of the hollow silica particles is released, and the particle size range of the hollow silica particles can be returned to its state before aggregation.

[0014] In this invention, aluminum atoms can be expressed in terms of Al2O3 by measuring the aluminum present on the surface of silica particles by leaching with an aqueous solution of at least one mineral acid selected from the group consisting of sulfuric acid, nitric acid, and hydrochloric acid. That is, the aluminum atoms are bonded to the hollow silica particles in Al2O3 equivalent proportions (A) of the mass of SiO2 in the hollow silica particles, where the mass of aluminum atoms measured by leaching is 100-20000 ppm / SiO2, or 100-15000 ppm / SiO2, 100-10000 ppm / SiO2, 200-5000 ppm / SiO2, 500-5000 ppm / SiO2, or 800-3000 ppm / SiO2 relative to the mass of SiO2 in the hollow silica particles. The presence of aluminum atoms on the surface of the silica particles to form aluminosilicate sites is important for dispersion in solvents and resins. Aluminum atoms present as aluminosilicate on the surface of silica particles can be leached (eluted) by adding an aqueous solution of at least one mineral acid selected from the group consisting of sulfuric acid, nitric acid, and hydrochloric acid. The aluminum atoms are then leached into a structure similar to aluminum salt, aluminum oxide, or aluminum hydroxide, and the aluminum atoms can be measured from the solution using an ICP emission spectrometer and expressed in terms of Al2O3. In particular, a method using an aqueous nitric acid solution is used for leaching. The aqueous nitric acid solution used for leaching can have a pH in the range of 0.5 to 4.0, 0.5 to 3.0, 0.5 to 2.0, or 1.0 to 1.5, and typically an aqueous nitric acid solution with a pH of 1.0 can be used. For example, 100 mL of the above aqueous nitric acid solution can be added to 1 g of silica and held at a temperature of 20 to 70°C or 40 to 60°C for 10 to 24 hours to elute aluminum compounds from the surface of the silica particles, which can then be used as an analytical sample.

[0015] In this invention, the silica particle surface can be defined as the region in which aluminum compounds can be eluted by the above-mentioned leaching. This is done by evaporating the solvent from a silica sol, further drying the silica gel at 250°C, grinding it to obtain silica powder, adding 20 mL of pH 1.0 aqueous nitric acid solution to 0.2 g of the silica powder, shaking thoroughly, holding in a constant temperature bath at 50°C for 17 hours, and then measuring the aluminum content in the filtrate obtained by centrifugal filtration using an ICP emission spectrometer. The amount of aluminum (Al2O3 / SiO2) (ppm) bound to the silica particle surface is then determined by dividing the aluminum content, converted to Al2O3, by the mass of the silica powder. Furthermore, even when forming aluminosilicate on the surface of silica particles, depending on the manufacturing method, aluminosilicate may be selectively formed not only on the surface but also inside the silica particles. The total mass of aluminum atoms present in the hollow silica particles, including both the surface and the interior, is bonded to the silica particles in the ratio (B) of Al2O3 to the mass of SiO2 in the hollow silica particles, in the range of 120-50000 ppm / SiO2, 500-20000 ppm / SiO2, 500-10000 ppm / SiO2, 1000-5000 ppm / SiO2, or 1000-4000 ppm / SiO2.

[0016] The above ratio (A) / ratio (B), which is the ratio of aluminum present on the surface of silica particles and throughout the silica particles, can be set to a range of 0.001 to 1.0, or 0.01 to 1.0, or 0.1 to 1.0, or 0.3 to 1.0, or 0.4 to 1.0. By dissolving silica particles in an aqueous hydrofluoric acid solution and measuring the amount of aluminum atoms present throughout the silica particles, the amount can be expressed in terms of Al2O3. In other words, the amount of aluminum atoms present as aluminosilicate throughout the silica particles can be expressed by dissolving them in an aqueous hydrofluoric acid solution. The solution can be measured using an ICP emission spectrometer, and the amount of aluminum atoms present throughout the silica particles can be expressed in terms of Al2O3. The hydrofluoric acid aqueous solution can be any concentration that can dissolve the silica particles; for example, a 48% by mass hydrofluoric acid aqueous solution can be used. In addition, to completely dissolve the silica particles, the amount of hydrofluoric acid aqueous solution used must be at least equivalent to the amount of silica particles, preferably in molar ratios of 1.1 to 1000 equivalents.

[0017] As aluminosilicate sites are formed on the surface of silica particles in this manner, the amount of negative charge (surface charge) of hollow silica particles present on the surface of the silica particles is measured in the range of 5 to 250 μeq / g, 5 to 150 μeq / g, 5 to 100 μeq / g, 25 to 150 μeq / g, or 25 to 100 μeq / g per gram of SiO2. The hollow silica particles described above can be obtained as a hollow silica sol dispersed in a dispersion medium. A hollow silica sol can be obtained in which hollow silica particles are dispersed in a dispersion medium, and the average particle size measured by dynamic light scattering is 20 to 150 nm. Hollow silica is obtained by forming an outer shell mainly composed of silica on the surface of a core-like portion called a template in a dispersion medium, and then removing the core-like portion. In this state, it is a hollow silica aqueous sol. The hollow silica aqueous sol obtained in this way can be subjected to solvent replacement with an alcohol solvent as an organic solvent. The alcohol solvent is preferably an alcohol having 1 to 5 carbon atoms, which may have ether bonds, and examples include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, propylene glycol monomethyl ether, and propylene glycol monoethyl ether. After that, it can be coated with a silane compound if desired, and then subjected to solvent replacement with another organic solvent.

[0018] In this invention, examples of organic solvents include alcohols, ketones, ethers, amides, ureas, and esters having 1 to 10 carbon atoms. Alcohols with 1 to 10 carbon atoms are aliphatic alcohols, including primary, secondary, and tertiary alcohols. These alcohols can also be polyhydric alcohols, such as dihydric and trihydric alcohols.

[0019] Examples of monohydric primary alcohols include methanol, ethanol, 1-propanol, 1-butanol, and 1-hexanol. Examples of monohydric secondary alcohols include 2-propanol, 2-butanol, cyclohexanol, propylene glycol monomethyl ether, and propylene glycol monoethyl ether. Examples of monohydric tertiary alcohols include tert-butyl alcohol. Examples of dihydric alcohols include methanediol, ethylene glycol, and propylene glycol. Examples of trihydric alcohols include glycerin.

[0020] Aliphatic ketones with 1 to 10 carbon atoms are preferably used as ketones. Examples include acetone, methyl ethyl ketone, diethyl ketone, methyl propyl ketone, methyl isobutyl ketone, methyl amyl ketone, cyclohexanone, and methylcyclopentanone. Aliphatic ethers with 1 to 10 carbon atoms are preferably used as ethers. Examples include dimethyl ether, ethyl methyl ether, diethyl ether, tetrahydrofuran, and 1,4-dioxane.

[0021] Examples of amides having 5 to 20 carbon atoms include N-methylpyrrolidone, dimethylacetamide, and diethylacetamide. Examples of ureas with 5 to 20 carbon atoms include tetramethylurea and 1,3-dimethyl-2-imi. Examples include dazolidinone. Aliphatic esters with 1 to 10 carbon atoms can be preferably used as esters. Examples include methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl acrylate, ethyl acrylate, propyl acrylate, dimethyl maleate, diethyl maleate, dipropyl maleate, dimethyl adipate, diethyl adipate, and dipropyl adipate.

[0022] In the hollow silica aqueous sol and hollow silica organic solvent sol, which are the raw materials mentioned above, the hollow silica particles can have an average particle diameter in the range of 20-150 nm, 30-150 nm, 40-150 nm, 50-150 nm, 50-120 nm, or 50-100 nm, as determined by dynamic light scattering (DLS). Furthermore, the average primary particle diameter observed using a transmission electron microscope can be in the range of 20-150 nm, 30-150 nm, 40-150 nm, 50-150 nm, 50-120 nm, or 50-100 nm.

[0023] Furthermore, the specific surface area (C) obtained by the BET method (nitrogen gas adsorption method) is 18-200 m². 2 / g, or 50-160m 2 / g, or 60-160m 2 / g, or 70-160m 2 / g, or 80-150m 2 It can be set to / g. Furthermore, the specific surface area (D) calculated from a transmission electron microscope is 18-136 m². 2 / g, or 18-90m 2 / g, or 18-68m 2 / g, or 18-54m 2 / g, or 18-27m 2 / g, or 18-23m 2 It can be set to / g.

[0024] Furthermore, the ratio of [specific surface area (C) calculated by the BET method (nitrogen gas adsorption method)] / [specific surface area (D) calculated from a transmission electron microscope] can be set within the range of 1.40 to 5.00, or 1.40 to 3.50, or 1.50 to 3.00, or 1.50 to 2.80. When the above (C) / (D) value is close to 1.0, it indicates a solid silica particle with no space inside the outer shell of the silica particle, and when the above (C) / (D) value exceeds 1.0, it indicates a hollow silica particle with space inside the outer shell of the silica particle. Furthermore, the outer shell thickness of hollow silica particles, as observed by transmission electron microscopy, can be manufactured in the range of 3.0 to 15.0 nm, 4.0 to 12.0 nm, or 5.0 to 10.0 nm. Furthermore, the refractive index of the hollow silica particles can be obtained in the range of 1.20 to 1.45, 1.20 to 1.40, or 1.25 to 1.40.

[0025] Furthermore, hollow silica sols have a concentration of SiO2 particles of 1 to 50% by mass, or 5 to 40% by mass, and can typically be used at 10 to 30% by mass. The pH of the above sol can be adjusted from acidic to alkaline. Adjustment to acidity is achieved by adding inorganic or organic acids. Adjustment to alkalinity is achieved by adding inorganic or organic bases; amines can be added as organic bases for pH adjustment and surface charge adjustment. The pH can be set to less than 7 on the acidic side and between 7 and 13 on the alkaline side.

[0026] The aqueous sol of hollow silica can be set to a pH range of, for example, 2.0 to 6.0 or 2.0 to 4.5 before the addition of amine, and can be adjusted to a range of, for example, 3.0 to 10.0 or 3.0 to 9.0 by adding amine. In the case of an organic solvent sol, the above pH is the pH when the organic solvent sol is mixed with an equal mass of pure water in a 1:1 ratio. The pH can be measured when an organic solvent that can be mixed with water is used, but if the solvent is to be replaced with a hydrophobic organic solvent later, it is preferable to measure the pH at the methanol solvent sol stage beforehand. For example, for hydrophilic organic solvents such as methanol sol and propylene glycol monomethyl ether sol, measurements can be taken using a solution prepared by mixing pure water and the sol in a mass ratio of 1:1. For hydrophobic organic solvents such as methyl ethyl ketone sol, measurements can be taken using a solution prepared by mixing pure water, methanol, and methyl ethyl ketone sol in a mass ratio of 1:1:1.

[0027] Hollow silica organic solvent sols are formed by solvent substitution of an aqueous medium with an alcohol solvent having 1 to 5 carbon atoms, and then with an organic solvent. However, water can remain in the process. For example, at the alcohol sol stage of hollow silica, residual water may be present in the sol at a concentration of 0.1 to 3.0% by mass, or 0.1 to 1.0% by mass. Furthermore, at the organic solvent sol stage of hollow silica (where the dispersion medium is an organic solvent other than alcohol), it may contain 0.01 to 0.5% by mass of residual water. Furthermore, in hollow silica organic solvent sols, the viscosity can be set in the range of 1.0 to 10.0 mPa·s.

[0028] The hollow silica sol of the present invention can be to which an amine can be added. The amine used in this invention can be a water-soluble amine with a water solubility of 80 g / L or more, or 100 g / L or more. The hollow silica aqueous sol, which is the raw material, and the hollow silica organic solvent sol obtained by solvent substitution, can contain an amine, or an amine and ammonia. The amine can be added and contained in a range of 0.001 to 10% by mass, 0.01 to 10% by mass, or 0.1 to 10% by mass relative to the SiO2 of the hollow silica particles. The amine, or the amine and ammonia, can be expressed as the total nitrogen content in the hollow silica particle organic solvent sol, for example, in the range of 10 to 100,000 ppm, 100 to 10,000 ppm, 100 to 3,000 ppm, or 100 to 2,000 ppm, typically in the range of 200 to 2,000 ppm.

[0029] The above-mentioned amines include aliphatic amines and aromatic amines, but aliphatic amines are preferably used. At least one amine selected from the group consisting of primary, secondary, and tertiary amines having 1 to 10 carbon atoms can be used. These amines are water-soluble and are at least one amine selected from the group consisting of primary, secondary, and tertiary amines having 1 to 10 carbon atoms. Examples of primary amines include monomethylamine, monoethylamine, monopropylamine, monoisopropylamine, monobutylamine, monoisobutylamine, monosecbutylamine, monotertbutylamine, monomethanolamine, monoethanolamine, monopropanolamine, monoisopropanolamine, monobutanolamine, monoisobutanolamine, monosecbutanolamine, and monotertbutanolamine.

[0030] Examples of secondary amines include dimethylamine, diethylamine, dipropylamine, diisopropylamine, N-methylethylamine, N-ethylisobutylamine, dimethanolamine, diethanolamine, dipropanolamine, diisopropanolamine, N-methanolethylamine, N-methylethanolamine, N-ethanolisobutylamine, and N-ethylisobutanolamine. Tertiary amines include trimethylamine, triethylamine, tripropylamine, triisopropylamine, tributylamine, triisobutylamine, trisecbutylamine, tritertbutylamine, trimethanolamine, tripropanolamine, triisopropanolamine, tributanolamine, triisobutanolamine, trisecbutanolamine, tritertbutanolamine, tripentylamine, ethyl 3-(dimethylamino)acrylate, ethyl 2-(dimethylamino)acrylate, ethyl 2-(dimethylamino)methacrylate, and ethyl 2-(diethylamino)acrylate. Examples include 2-(diethylamino)ethyl methacrylate.

[0031] The aqueous solubility of the above amines can preferably be 80 g / L or more, or 100 g / L or more. Primary and secondary amines are preferred, with secondary amines being preferred due to their low volatility and high solubility. Examples include diisopropylamine and diethanolamine. In this invention, by including the above-mentioned amine, the surface charge of hollow silica particles can be set to 5 μeq / g or more, or 25 μeq / g or more, in terms of SiO2 equivalent, per gram. Typically, it can be set in the range of 5 to 250 μeq / g, 25 to 250 μeq / g, 25 to 100 μeq / g, or 25 to 80 μeq / g. In this invention, by adjusting the type and amount of amine mentioned above, it is possible to adjust the surface charge of hollow silica particles to any desired surface charge.

[0032] In this invention, the surface of hollow silica particles can be coated with a silane compound. The above silane compound can be coated with a hydrolysis product of at least one silane compound selected from the group consisting of formulas (1) and (2). In formula (1), R 1 Each of these is an organic group having an alkyl group, a halogenated alkyl group, an alkenyl group, an aryl group, or a polyether group, an epoxy group, a (meth)acryloyl group, a mercapto group, an amino group, a ureido group, or a cyano group, and is bonded to a silicon atom by a Si-C bond, R 2 Each of the following represents an alkoxy group, an acyloxy group, or a halogen group, and a represents an integer from 1 to 3. In formula (2), R 3 These are alkyl groups with 1 to 3 carbon atoms, or aryl groups with 6 to 30 carbon atoms, and are bonded to silicon atoms by Si-C bonds, R 4 Each of the following groups represents an alkoxy group, an acyloxy group, or a halogen group; Y represents an alkylene group, an NH group, or an oxygen atom; b is an integer from 1 to 3; c is an integer of 0 or 1; and d is an integer from 1 to 3.

[0033] The above alkyl groups are alkyl groups having 1 to 18 carbon atoms, for example, methyl group, ethyl group, n-propyl group, i-propyl group, cyclopropyl group, n-butyl group, i-butyl group, s-butyl group, t-butyl group, cyclobutyl group, 1-methyl-cyclopropyl group, 2-methyl-cyclopropyl group, n-pentyl group, 1-methyl-n-butyl group, 2-methyl-n-butyl group, 3-methyl-n-butyl group, 1,1-dimethyl-n-propyl group, 1,2-dimethyl-n-propyl group, 2,2-dimethyl-n-propyl group, 1-ethyl-n-propyl group, cyclopentyl group, 1-methyl-cyclobutyl group, 2-methyl-cyclobutyl group, 3-methyl-cyclobutyl group, 1,2-dimethyl-cyclopropyl group, 2,3-dimethyl-cyclopropyl group, 1-ethyl-cyclopropyl group, 2-ethyl-cyclopropyl group, n-hexyl group, 1-methyl-n-pentyl group, 2-methyl-n-pentyl group, 3-methyl-n-pentyl group, 4-methyl-n-pentyl group, 1,1-dimethyl-n-butyl group, 1,2-dimethyl-n-butyl group, 1,3 -dimethyl-n-butyl group, 2,2-dimethyl-n-butyl group, 2,3-dimethyl-n-butyl group, 3,3-dimethyl-n-butyl group, 1-ethyl-n-butyl group, 2-ethyl-n-butyl group, 1,1,2-trimethyl-n-propyl group, 1,2,2-trimethyl-n-propyl group, 1-ethyl-1-methyl-n-propyl group, 1-ethyl-2-methyl-n-propyl group, cyclohexyl group, 1-methyl-cyclopentyl group, 2-methyl-cyclopentyl group, 3-methyl-cyclopentyl group, 1-ethyl-cyclo Butyl group, 2-ethyl-cyclobutyl group, 3-ethyl-cyclobutyl group, 1,2-dimethyl-cyclobutyl group, 1,3-dimethyl-cyclobutyl group, 2,2-dimethyl-cyclobutyl group, 2,3-dimethyl-cyclobutyl group, 2,4-dimethyl-cyclobutyl group, 3,3-dimethyl-cyclobutyl group, 1-n-propyl-cyclopropyl group, 2-n-propyl-cyclopropyl group, 1-i-propyl-cyclopropyl group, 2-i-propyl-cyclopropyl group, 1,2,2-trimethyl-cyclopropyl group, 1, Examples of such groups include, but are not limited to, 2,3-trimethylcyclopropyl group, 2,2,3-trimethylcyclopropyl group, 1-ethyl-2-methylcyclopropyl group, 2-ethyl-1-methylcyclopropyl group, 2-ethyl-2-methylcyclopropyl group and 2-ethyl-3-methylcyclopropyl group, hexyl group, heptyl group, octyl group, nonyl group, decyl group, undecyl group, dodecyl group, tridecyl group, tetradecyl group, pentadecyl group, hexadecyl group, heptadecyl group, octadecyl group, etc. Furthermore, alkylene groups can be derived from the alkyl groups mentioned above.

[0034] The aryl group mentioned above is an aryl group having 6 to 30 carbon atoms, and examples include the phenyl group, naphthyl group, anthracene group, and pyrene group. Alkenyl groups are alkenyl groups having 2 to 10 carbon atoms, including ethenyl group, 1-propenyl group, 2-propenyl group, 1-methyl-1-ethenyl group, 1-butenyl group, 2-butenyl group, 3-butenyl group, 2-methyl-1-propenyl group, 2-methyl-2-propenyl group, 1-ethylethenyl group, 1-methyl-1-propenyl group, 1-methyl-2-propenyl group, 1-pentenyl group, 2-pentenyl group, 3-pentenyl group, 4-pentenyl group, 1-n-propylethenyl group, 1-methyl-1-butenyl group, 1-methyl-2-butenyl group, 1-methyl-3-butenyl group, 2-ethyl-2-propenyl group, 2-methyl-1-butenyl group, 2-methyl-2-butenyl group, 2-methyl-3-butenyl group, and 3 Examples of but not limited to the following are methyl-1-butenyl group, 3-methyl-2-butenyl group, 3-methyl-3-butenyl group, 1,1-dimethyl-2-propenyl group, 1-i-propylethenyl group, 1,2-dimethyl-1-propenyl group, 1,2-dimethyl-2-propenyl group, 1-cyclopentenyl group, 2-cyclopentenyl group, 3-cyclopentenyl group, 1-hexenyl group, 2-hexenyl group, 3-hexenyl group, 4-hexenyl group, 5-hexenyl group, 1-methyl-1-pentenyl group, 1-methyl-2-pentenyl group, 1-methyl-3-pentenyl group, 1-methyl-4-pentenyl group, 1-n-butylethenyl group, 2-methyl-1-pentenyl group, 2-methyl-2-pentenyl group, etc.

[0035] The alkoxy groups mentioned above include, but are not limited to, alkoxy groups having 1 to 10 carbon atoms, such as methoxy group, ethoxy group, n-propoxy group, i-propoxy group, n-butoxy group, i-butoxy group, s-butoxy group, t-butoxy group, n-pentyloxy group, 1-methyl-n-butoxy group, 2-methyl-n-butoxy group, 3-methyl-n-butoxy group, 1,1-dimethyl-n-propoxy group, 1,2-dimethyl-n-propoxy group, 2,2-dimethyl-n-propoxy group, 1-ethyl-n-propoxy group, and n-hexyloxy group. The above-mentioned acyloxy groups, which have 2 to 10 carbon atoms, include, but are not limited to, methyl carbonyloxy group, ethyl carbonyloxy group, n-propyl carbonyloxy group, i-propyl carbonyloxy group, n-butyl carbonyloxy group, i-butyl carbonyloxy group, s-butyl carbonyloxy group, t-butyl carbonyloxy group, n-pentyl carbonyloxy group, 1-methyl-n-butyl carbonyloxy group, 2-methyl-n-butyl carbonyloxy group, 3-methyl-n-butyl carbonyloxy group, 1,1-dimethyl-n-propyl carbonyloxy group, 1,2-dimethyl-n-propyl carbonyloxy group, 2,2-dimethyl-n-propyl carbonyloxy group, 1-ethyl-n-propyl carbonyloxy group, n-hexyl carbonyloxy group, 1-methyl-n-pentyl carbonyloxy group, and 2-methyl-n-pentyl carbonyloxy group. Examples of the halogen groups mentioned above include fluorine, chlorine, bromine, and iodine. Examples of organic groups having a polyether group include polyetherpropyl groups having an alkoxy group. For example, (CH3O)3SiC3H6(OC2H4)nOCH3 is an example, where n can be in the range of 1 to 100 or 1 to 10.

[0036] Examples of organic groups having an epoxy group include the 2-(3,4-epoxycyclohexyl)ethyl group and the 3-glycidoxypropyl group. The above term "(meth)acryloyl group" refers to both an acryloyl group and a methacryloyl group. Examples of organic groups having a (meth)acryloyl group include 3-methacryloxypropyl group and 3-acryloxypropyl group.

[0037] An example of an organic group containing a mercapto group is the 3-mercaptopropyl group. Examples of organic groups having an amino group include 2-aminoethyl group, 3-aminopropyl group, N-2-(aminoethyl)-3-aminopropyl group, N-(1,3-dimethylbutylidene)aminopropyl group, N-phenyl-3-aminopropyl group, and N-(vinylbenzyl)-2-aminoethyl-3-aminopropyl group. An example of an organic group having a ureido group is the 3-ureidopropyl group. An example of an organic group having a cyano group is the 3-cyanopropyl group. A compound capable of forming the above formula (2) trimethylsilyl group on the surface of silica particles is preferred.

[0038] Examples of such compounds are listed below. [ka] In the above formula, R 12 The group is an alkoxy group, such as a methoxy group or an ethoxy group. The above silane compound can be a silane compound manufactured by Shin-Etsu Chemical Co., Ltd. This process involves the reaction of hydroxyl groups, such as silanol groups in the case of silica particles, with the silane compound on the surface of silica particles to coat the surface of the silica particles with the silane compound via siloxane bonds. The reaction temperature can be from 20°C to the boiling point of the dispersion medium, but can be carried out in the range of 20°C to 100°C, for example. The reaction time can be approximately 0.1 to 6 hours.

[0039] The above silane compound is defined as having a coating amount on the silica particle surface, with a silicon atom count of 0.1 atoms / nm in the silane compound. 2 ~6.0 pieces / nm 2 The silica particle surface can be coated by adding a silane compound equivalent to the coating amount to the silica sol. The hydrolysis of the above silane compounds requires water, but if the solvent is an aqueous sol, then those water A solvent is used. When an aqueous medium is replaced with an organic solvent, the water remaining in the solvent can be used. For example, water present at 0.01 to 1% by mass can be used. Furthermore, hydrolysis can be carried out with or without a catalyst.

[0040] When hydrolysis is performed without a catalyst, the silica particle surface is on the acidic side. When a catalyst is used, examples of hydrolysis catalysts include metal chelate compounds, organic acids, inorganic acids, organic bases, and inorganic bases. Examples of metal chelate compounds as hydrolysis catalysts include triethoxy mono(acetylacetonate) titanium and triethoxy mono(acetylacetonate) zirconium. Examples of organic acids as hydrolysis catalysts include acetic acid and oxalic acid. Examples of inorganic acids as hydrolysis catalysts include hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid, and phosphoric acid. Examples of organic bases as hydrolysis catalysts include pyridine, pyrrole, piperazine, and quaternary ammonium salts. Examples of inorganic bases as hydrolysis catalysts include ammonia, sodium hydroxide, and potassium hydroxide. The organic acid is at least one organic acid selected from the group consisting of divalent aliphatic carboxylic acids, aliphatic oxycarboxylic acids, amino acids, and chelating agents. Divalent aliphatic carboxylic acids include oxalic acid, malonic acid, and succinic acid; aliphatic oxycarboxylic acids include glycolic acid, lactic acid, malic acid, tartaric acid, and citric acid; amino acids include glycine, alanine, valine, leucine, serine, and trionine; and chelating agents include ethylenediaminetetraacetic acid, L-aspartic acid-N,N-diacetic acid, and diethylenetriaminepentaacetic acid. Organic acid salts include alkali metal salts, ammonium salts, and amine salts of the above organic acids. Examples of alkali metals include sodium and potassium.

[0041] In the present invention, a film-forming composition comprising the above-mentioned hollow silica organic solvent sol and an organic resin or polysiloxane can be obtained. A film-forming composition can be obtained by selecting and mixing an organic resin or polysiloxane with a thermosetting or photocurable resin. The cured product can then be obtained by including a curing agent such as an amine-based curing agent, an acid anhydride-based curing agent, a radical-generating curing agent (thermal radical generator, photoradical generator), or an acid-generating curing agent (thermal acid generator, or photoacid generator). This composition allows for the formation of a cured product by applying or filling a substrate with a film-forming composition containing an organic resin or polysiloxane and a curing agent, followed by heating, light irradiation, or a combination thereof. Examples of organic resins and polysiloxanes (curable resins) include resins having functional groups such as epoxy groups or (meth)acryloyl groups, and isocyanate resins. For example, photocurable polyfunctional acrylates can be preferably used.

[0042] Examples of polyfunctional acrylates include those having two, three, four, or more functional groups in the molecule, such as neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and dipentaerythritol hexa(meth)acrylate. These polyfunctional acrylates can also be described below. [ka] [ka] [ka] [ka]

[0043] The film-forming composition of the present invention may contain a surfactant (leveling agent). As surfactants (leveling agents), anionic surfactants, cationic surfactants, amphoteric surfactants, nonionic surfactants, and silicone-based surfactants can be used. The surfactant (leveling agent) can be added to the organic resin or polysiloxane in a range of 0.01 to 5 phr, or 0.01 to 1 phr. Examples of anionic surfactants used in the present invention include sodium and potassium salts of fatty acids, alkylbenzene sulfonates, higher alcohol sulfates, polyoxyethylene alkyl ether sulfates, α-sulfo fatty acid esters, α-olefin sulfonates, monoalkyl phosphates, and alkanesulfonates. For example, alkylbenzene sulfonates include sodium salts, potassium salts, and lithium salts, such as sodium C10-C16 alkylbenzene sulfonate, C10-C16 alkylbenzene sulfonic acid, and sodium alkylnaphthalene sulfonate.

[0044] Examples of higher alcohol sulfate salts include sodium dodecyl sulfate (sodium lauryl sulfate), triethanolamine lauryl sulfate, and triethanolammonium lauryl sulfate, all of which have 12 carbon atoms. Polyoxyethylene alkyl ether sulfates include polyoxyethylene styrene-phenyl ether sodium sulfate, polyoxyethylene styrene-phenyl ether ammonium sulfate, polyoxyethylene decyl ether sodium sulfate, polyoxyethylene decyl ether ammonium sulfate, polyoxyethylene lauryl ether sodium sulfate, polyoxyethylene lauryl ether ammonium sulfate, polyoxyethylene tridecyl ether sodium sulfate, and polyoxyethylene oleyl cetyl ether sodium sulfate. Examples of alpha-olefin sulfonates include sodium alpha-olefin sulfonate.

[0045] Examples of alkanesulfonates include sodium 2-ethylhexyl sulfate. Examples of cationic surfactants used in the present invention include alkyltrimethylammonium salts, dialkyldimethylammonium salts, alkyldimethylbenzylammonium salts, and amine salt-based agents. Alkyltrimethylammonium salts are quaternary ammonium salts that have chloride ions or bromide ions as counterions. Examples include dodecyltrimethylammonium chloride, cetyltrimethylammonium chloride, coconut alkyltrimethylammonium chloride, and alkyl(C16-18)trimethylammonium chloride. Dialkyldimethylammonium salts have two lipophilic main chains and two methyl groups. Bis(hydrogenated tallow)dimethylammonium chloride is an example. Other examples include didecyldimethylammonium chloride, dialkyldimethylammonium chloride, dihydrogenated tallow alkyldimethylammonium chloride, and dialkyl(C14-18)dimethylammonium chloride.

[0046] Alkyldimethylbenzylammonium salts are quaternary ammonium salts having one lipophilic main chain, two methyl groups, and one benzyl group, and an example is benzaukonium chloride. Another example is alkyl(C8-18)dimethylbenzylammonium chloride. Examples of amine salt-based agents include those in which ammonia hydrogen atoms are substituted with one or more hydrocarbon groups, such as N-methylbishydroxyethylamine fatty acid ester hydrochloride. Examples of amphoteric surfactants used in the present invention include N-alkyl-β-alanine type alkylamino fatty acid salts, alkyl carboxybetaine type alkyl betaines, and N,N-dimethyldodecylamine oxide type alkylamine oxides. Examples of these include lauryl betaine, stearyl betaine, 2-alkyl-N-carboxymethyl-N-hydroxyethylimidazolinium betaine, and lauryldimethylamine oxide.

[0047] The nonionic surfactant used in the present invention is selected from polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, alkyl glucosides, polyoxyethylene fatty acid esters, sucrose fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, and fatty acid alkanolamides. For example, poly Examples of oxyethylene alkyl ethers include polyoxyethylene dodecyl ether (polyoxyethylene lauryl ether), polyoxyalkylene lauryl ether, polyoxyethylene tridecyl ether, polyoxyalkylene tridecyl ether, polyoxyethylene myristyl ether, polyoxyethylene cetyl ether, polyoxyethylene oleyl ether, polyoxyethylene stearyl ether, polyoxyethylene behenyl ether, polyoxyethylene-2-ethylhexyl ether, and polyoxyethylene isodecyl ether. Examples of polyoxyethylene alkylphenol ethers include polyoxyethylene styrene-modified phenyl ether, polyoxyethylene nonylphenyl ether, polyoxyethylene disstyrene-modified phenyl ether, and polyoxyethylene tripenzylphenyl ether.

[0048] Examples of alkyl glucosides include decyl glucoside and lauryl glucoside. Examples of polyoxyethylene fatty acid esters include polyoxyethylene monolaurate, polyoxyethylene monostearate, polyoxyethylene monooleate, polyethylene glycol distearate, polyethylene glycol diolate, and polypropylene glycol diolate. Examples of sorbitan fatty acid esters include sorbitan monocaprylate, sorbitan monolaurate, sorbitan monomyristate, sorbitan monopalmitate, sorbitan monostearate, sorbitan distearate, sorbitan tristearate, sorbitan monooleate, sorbitan trioleate, sorbitan monosesquioleate, and their ethylene oxide adducts.

[0049] Examples of polyoxyethylene sorbitan fatty acid esters include polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan tristearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan trioleate, and polyoxyethylene sorbitan triisostearate. Other examples of fatty acid alkanolamides include coconut oil fatty acid diethanolamide, beef tallow fatty acid diethanolamide, lauric acid diethanolamide, and oleic acid diethanolamide.

[0050] Furthermore, examples include polyoxyethylene polyoxypropylene glycol, polyoxyethylene fatty acid esters, polyoxyalkyl ethers or polyoxyalkyl glycols, polyoxyethylene hydrogenated castor oil ether, sorbitan fatty acid ester alkyl ether, alkyl polyglucoside, sorbitan monooleate, and sucrose fatty acid ester. Silicone-based surfactants can be used. Silicone-based surfactants are compounds that have repeating units containing siloxane bonds in their main chain. The weight-average molecular weight of silicone-based surfactants can be in the range of 500 to 50,000. These may also be modified silicone-based surfactants, and include structures in which organic groups are introduced to the side chains and / or terminals of polysiloxane. Examples of organic groups include amino groups, epoxy groups, alicyclic epoxy groups, carbinol groups, mercapto groups, carboxyl groups, aliphatic ester groups, aliphatic amide groups, and polyether groups. Silicone-based surfactants include the following product names: Toray Silicone DC3PA, Toray Silicone SH7PA, Toray Silicone DC11PA, Toray Silicone SH21PA, Toray Silicone SH28PA, Toray Silicone SH29PA, Toray Silicone SH30PA, Toray Silicone SH8400 (all manufactured by Toray Dow Corning Co., Ltd.), Silwet L-77, L-7280, L-7001, L-7002, L-7200, L-7210, L-7220, L-7230, L7500, L-7600, L-7602, L-7604, L-7605, L-7622, ​​L-7657, L-8500, L-86 Examples include 10 (manufactured by Momentive Performance Materials), KP-341, KF-6001, KF-6002 (manufactured by Shin-Etsu Silicone Co., Ltd.), BYK307, BYK323, BYK330 (manufactured by Bic Chemie). For example, product name L-7001 (manufactured by DOWSIL) can be suitably used as a polyether-modified silicone.

[0051] In the present invention, a film-forming composition can be obtained that contains the above-mentioned organic solvent sol and an organic resin or polysiloxane. The film-forming composition can be obtained by removing the organic solvent from the organic solvent sol to obtain a film-forming composition containing hollow silica particles and an organic resin. In the case of a thermosetting film-forming composition as described above, a thermosetting agent can be added to a functional group-containing resin such as an epoxy group or a (meth)acryloyl group in an amount of 0.01 to 50 phr, or in an amount of 0.01 to 10 phr. For example, the thermosetting agent can be contained in an amount of 0.5 to 1.5 equivalents, preferably 0.8 to 1.2 equivalents, relative to the functional group such as an epoxy group or a (meth)acryloyl group. The equivalent amount of the thermosetting agent relative to the curable resin is expressed as the equivalent ratio of the thermosetting agent to the functional group.

[0052] Examples of thermosetting agents include phenolic resins, amine-based curing agents, polyamide resins, imidazoles, polymer mercaptans, acid anhydrides, thermal radical generators, and thermal acid generators. Radical-generating curing agents, acid anhydride-based curing agents, and amine-based curing agents are particularly preferred. Although these thermosetting agents can be used by dissolving them in a solvent even if they are solid, evaporation of the solvent can lead to a decrease in density of the cured product, the formation of pores, a decrease in strength, and a decrease in water resistance. Therefore, it is preferable that the curing agent itself be liquid at room temperature and atmospheric pressure. Examples of phenolic resins include phenol novolac resins and cresol novolac resins.

[0053] Examples of amine-based curing agents include piperidine, N,N-dimethylpiperazine, triethylenediamine, 2,4,6-tris(dimethylaminomethyl)phenol, benzyldimethylamine, 2-(dimethylaminomethyl)phenol, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, diethylaminopropylamine, N-aminoethylpiperazine, di(1-methyl-2-aminocyclohexyl)methane, menthanediamine, isophoronediamine, diaminodicyclohexylmethane, 1,3-diaminomethylcyclohexane, xylenediamine, metaphenylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, 3,3'-diethyl-4,4'-diaminodiphenylmethane, and diethyltoluenediamine. Among these, liquid diethylenetriamine, triethylenetetramine, tetraethylenepentamine, diethylaminopropylamine, N-aminoethylpiperazine, di(1-methyl-2-aminocyclohexyl)methane, mensendiamine, isophoronediamine, diaminodicyclohexylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, diethyltoluenediamine, etc., can be preferably used. Polyamide resins are produced by the condensation of dimer acid and polyamine, and are polyamidoamines having a primary amine and a secondary amine in their molecules.

[0054] Examples of imidazoles include 2-methylimidazole, 2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, and epoxyimidazole adduct. Polymercaptans are, for example, those in which mercaptan groups are present at the ends of polypropylene glycol chains or polyethylene glycol chains, and are preferably in liquid form.

[0055] As an acid anhydride-based curing agent, an anhydride of a compound having multiple carboxyl groups in one molecule is used. Preferred. Examples of these acid anhydride-based curing agents include phthalic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenonetetracarboxylic anhydride, ethylene glycol bistrimellitate, glycerol trimellitate, maleic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, endomethylenetetrahydrophthalic anhydride, methylendomethylenetetrahydrophthalic anhydride, methylbutenyltetrahydrophthalic anhydride, dodecenyl succinic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, succinic anhydride, methylcyclohexendicarboxylic anhydride, and chloride anhydride. Examples of thermal acid generators include sulfonium salts and phosphonium salts, but sulfonium salts are preferred. For example, the following compounds can be cited. [ka] R can be an alkyl group having 1 to 12 carbon atoms or an aryl group having 6 to 20 carbon atoms, with alkyl groups having 1 to 12 carbon atoms being particularly preferred.

[0056] Among these, methyltetrahydrophthalic anhydride, methyl-5-norbornene-2,3-dicarboxylic acid anhydride (methylnadic anhydride, methylhymic anhydride), hydrogenated methylnadic anhydride, methylbutenyltetrahydrophthalic anhydride, dodecenyl succinic anhydride, methylhexahydrophthalic anhydride, and mixtures of methylhexahydrophthalic anhydride and hexahydrophthalic anhydride are preferred, as they are liquid at room temperature and atmospheric pressure. These liquid acid anhydrides have a viscosity of approximately 10 mPa·s to 1000 mPa·s when measured at 25°C. Examples of thermal radical generators include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-methylpropionic acid)dimethyl, 2,2'-azobis(2-methylpropionamidine) dihydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride, tert-butyl hydroperoxide, cumene hydroperoxide, di-tert-butyl peroxide, dicumyl peroxide, and benzoyl peroxide. These can be obtained from Tokyo Chemical Industry Co., Ltd.

[0057] Furthermore, when obtaining the above-mentioned cured product, a curing aid may be used in combination as appropriate. Examples of curing aids include organophosphorus compounds such as triphenylphosphine and tributylphosphine, quaternary phosphonium salts such as ethyltriphenylphosphonium bromide and methyltriphenylphosphonium diethyl phosphate, 1,8-diazabicyclo(5,4,0)undecane-7-ene, a salt of 1,8-diazabicyclo(5,4,0)undecane-7-ene and octic acid, zinc octyolate, and quaternary ammonium salts such as tetrabutylammonium bromide. These curing aids can be included in a ratio of 0.001 to 0.1 parts by mass per 1 part by mass of the curing agent. The composition is obtained by mixing a resin, a hardener, and optionally a curing aid to obtain a thermosetting varnish. These can be mixed in a reaction vessel using a stirring blade or kneader.

[0058] Mixing is carried out by a heating method, at a temperature of 60°C to 100°C for 0.5 to 1 hour. . The resulting curable film-forming composition is a thermosetting coating composition and has a suitable viscosity for use, for example, as a liquid encapsulant. The liquid thermosetting film-forming composition can be adjusted to any viscosity and can be partially encapsulated at any point on an LED or the like for use as a transparent encapsulant by casting, potting, dispensing, printing, etc. An epoxy resin cured body can be obtained by directly mounting the liquid thermosetting composition onto an LED or the like in liquid form using the method described above, and then drying and curing it. A thermosetting film-forming composition (thermosetting coating composition) is applied to a substrate and heated at a temperature of 80 to 200°C to obtain a cured product. In the case of a photocurable resin composition in the above-mentioned film-forming composition, a photocuring agent (photoradical generator, photoacid generator) can be added to a functional group-containing resin such as an epoxy group or a (meth)acryloyl group in an amount of 0.01 to 50 phr, or in an amount of 0.01 to 10 phr. For example, the photocuring agent (photoradical generator, photoacid generator) can be contained in an amount of 0.5 to 1.5 equivalents, preferably 0.8 to 1.2 equivalents, relative to a functional group such as an epoxy group or a (meth)acryloyl group. The equivalent amount of the photocuring agent relative to the curable resin is expressed as the equivalent ratio of the photocuring agent to the functional group. The photoradical generator is not particularly limited as long as it generates radicals directly or indirectly upon light irradiation.

[0059] Examples of photoradical generators and photoradical polymerization initiators include imidazole compounds, diazo compounds, bisimidazole compounds, N-arylglycine compounds, organic azide compounds, titanocene compounds, aluminate compounds, organic peroxides, N-alkoxypyridinium salt compounds, and thioxanthone compounds. Examples of azide compounds include p-azidobenzaldehyde, p-azidoacetophenone, p-azidobenzoic acid, p-azidobenzalacetophenone, 4,4'-diazidochalcone, 4,4'-diazidodiphenyl sulfide, and 2,6-bis(4'-azidobenzal)-4-methylcyclohexanone. Examples of diazo compounds include 1-diazo-4-N,N-dimethylaminobenzene chloride and 1-diazo-4-N,N-diethylaminobenzeneborofluoride. Examples of bisimidazole compounds include 2,2'-bis(o-chlorophenyl)-4,5,4',5'-tetrakis(3,4,5-trimethoxyphenyl)1,2'-bisimidazole and 2,2'-bis(o-chlorophenyl)4,5,4',5'-tetraphenyl-1,2'-bisimidazole. Examples of titanocene compounds include dicyclopentadienyl-titanium-dichloride, dicyclopentadienyl-titanium-bisphenyl, dicyclopentadienyl-titanium-bis(2,3,4,5,6-pentafluorophenyl), dicyclopentadienyl-titanium-bis(2,3,5,6-tetrafluorophenyl), dicyclopentadienyl-titanium-bis(2,4,6-trifluorophenyl), dicyclopentadienyl-titanium-bis(2,6-difluorophenyl), and dicyclopentadienyl Examples include titanium-bis(2,4-difluorophenyl), bis(methylcyclopentadienyl)-titanium-bis(2,3,4,5,6-pentafluorophenyl), bis(methylcyclopentadienyl)-titanium-bis(2,3,5,6-tetrafluorophenyl), bis(methylcyclopentadienyl)-titanium-bis(2,6-difluorophenyl), and dicyclopentadienyl-titanium-bis(2,6-difluoro-3-(1H-pyrrole-1-yl)-phenyl).

[0060] As photoradical generators, also include 1,3-di(tert-butyldioxycarbonyl)benzophenone, 3,3',4,4'-tetrakis(tert-butyldioxycarbonyl)benzophenone, 3-phenyl-5-isoxazolone, 2-mercaptobenzimidazole, 2,2-dimethoxy-1,2-diphenylethane-1-one, 1-hydroxycyclohexylphenyl-ketone, and 2-benzyl-2-dimethylamino-1- Examples include (4-morpholinophenyl)-butanone. These photoradical polymerization agents can be obtained, for example, from BASF, trade name IrgacureTPO (component: 2,4,6-trimethylbenzoyldiphenylphosphine oxide) (formula (c1-1-1)), from IGM RESINS, trade name Omnirad819 (component: bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide) (formula (c1-1-2)), and from IGM RESINS, trade name Irgacure 184 (component: 1-hydroxycyclohexylphenyl ketone) (formula (c1-1-3)). [ka]

[0061] The photoacid generator is not particularly limited as long as it generates acid directly or indirectly upon light irradiation. Specific examples of photoacid generators include triazine compounds, acetophenone derivative compounds, disulfone compounds, diazomethane compounds, sulfonic acid derivative compounds, iodonium salts, sulfonium salts, phosphonium salts, selenium salts and other onium salts, metallocene complexes, and iron arene complexes.

[0062] The onium salt used as the above photoacid generator is, for example, an iodonium salt such as diphenyliodonium chloride, diphenyliodonium trifluoromethanesulfonate, diphenyliodonium mesylate, diphenyliodonium tosylate, and diphenyliod Nium bromide, diphenyliodonium tetrafluoroborate, diphenyliodonium hexafluoroantimonate, diphenyliodonium hexafluoroarsenate, bis(p-tert-butylphenyl)iodonium hexafluorophosphate, bis(p-tert-butylphenyl)iodonium mesylate, bis(p-tert-butylphenyl)iodonium tosylate, bis(p-tert-butylphenyl)iodonium trifluoromethanesulfonate, bis(p-tert-butylphenyl)iodonium tetrafluoroborate, bis(p-tert-butylphenyl)iodonium chloride, bis(p-chlorophenyl)iodonium Examples include bis(alkylphenyl)iodonium salts such as bis(p-chlorophenyl)iodonium chloride, bis(p-chlorophenyl)iodonium tetrafluoroborate, and bis(4-t-butylphenyl)iodonium hexafluorophosphate, alkoxycarbonylalkoxy-trialkylaryliodonium salts (e.g., 4-[(1-ethoxycarbonyl-ethoxy)phenyl]-(2,4,6-trimethylphenyl)-iodonium hexafluorophosphate), and bis(alkoxyaryl)iodonium salts (e.g., bis(alkoxyphenyl)iodonium salts such as (4-methoxyphenyl)phenyliodonium hexafluoroantimonate).

[0063] Examples of sulfonium salts include triphenylsulfonium chloride, triphenylsulfonium bromide, tri(p-methoxyphenyl)sulfonium tetrafluoroborate, tri(p-methoxyphenyl)sulfonium hexafluorophosphonate, tri(p-ethoxyphenyl)sulfonium tetrafluoroborate, triphenylsulfonium triflate, triphenylsulfonium hexafluoroantimonate, triphenylsulfonium hexafluorophosphate, and other triphenylsulfonium salts, as well as sulfonium salts such as (4-phenylthiophenyl)diphenylsulfonium hexafluoroantimonate, (4-phenylthiophenyl)diphenylsulfonium hexafluorophosphate, bis[4-(diphenylsulfonio)phenyl]sulfide-bis-hexafluoroantimonate, bis[4-(diphenylsulfonio)phenyl]sulfide-bis-hexafluorophosphate, and (4-methoxyphenyl)diphenylsulfonium hexafluoroantimonate.

[0064] Examples of phosphonium salts include triphenylphosphonium chloride, triphenylphosphonium bromide, tri(p-methoxyphenyl)phosphonium tetrafluoroborate, tri(p-methoxyphenyl)phosphonium hexafluorophosphonate, tri(p-ethoxyphenyl)phosphonium tetrafluoroborate, 4-chlorobenzenediazonium hexafluorophosphate, and benzyltriphenylphosphonium hexafluoroantimonate. Examples include selenium salts such as triphenylselenium hexafluorophosphate and metallocene complexes such as (η5 or η6-isopropylbenzene)(η5-cyclopentadienyl)iron(II) hexafluorophosphate.

[0065] In addition, the following compounds can also be used as photoacid generators. [ka] [ka]

[0066] [ka] [ka]

[0067] [ka] [ka]

[0068] [ka] [ka] [ka]

[0069] Sulfonium salt compounds and iodonium salt compounds are preferred as photoacid generators. The anionic species is CF3SO3. - , C4F9SO3 - , C8F 17 SO3 - Camphor sulfonate anion, tosylate anion, BF4 - PF6 - AsF6 - and SbF6 - These are some examples. Anionic species such as phosphorus hexafluoride and antimony hexafluoride, which exhibit strong acidity, are particularly preferred. The film-forming composition of the present invention may optionally contain conventional additives. Examples of additives include pigments, colorants, thickeners, sensitizers, defoamers, coating improvers, lubricants, stabilizers (antioxidants, heat stabilizers, light stabilizers, etc.), plasticizers, dissolution accelerators, fillers, and antistatic agents. These additives may be used individually or in combination of two or more. Examples of methods for applying the film-forming composition of the present invention include flow coating, spin coating, spray coating, screen printing, casting, bar coating, curtain coating, roll coating, gravure coating, dipping, and slitting.

[0070] In this invention, a photocoating composition (film-forming composition) can be applied to a substrate and cured by light irradiation. Heating can also be performed before and after light irradiation. The thickness of the coating film can be selected from a range of approximately 0.01 μm to 10 mm, depending on the application of the cured material. For example, when used for photoresists, it can be approximately 0.05 to 10 μm (especially 0.1 to 5 μm); when used for printed circuit boards, it can be approximately 5 μm to 5 mm (especially 100 μm to 1 mm); and when used for optical thin films, it can be approximately 0.1 to 100 μm (especially 0.3 to 50 μm). When obtaining a transparent coating, the visible light transmittance of the coating can be 80% or more, or 90% or more, typically 90-96%.

[0071] When using a photoacid generator, the light used for irradiation or exposure may be, for example, gamma rays, X-rays, ultraviolet light, or visible light, and is usually visible light or ultraviolet light, especially ultraviolet light. The wavelength of the light is, for example, 150 to 800 nm, preferably 150 to 600 nm, and more preferably 150 to 400 nm. The amount of irradiation light varies depending on the thickness of the coating film, but is, for example, 2 to 20,000 mJ / cm². 2 Preferably 5 to 5000 mJ / cm² 2The degree can be adjusted accordingly. The light source can be selected according to the type of light to be exposed; for example, in the case of ultraviolet light, low-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, deuterium lamps, halogen lamps, laser light (helium-cadmium laser, excimer laser, etc.) can be used. The curing reaction of the composition proceeds upon such light irradiation. When using a thermal acid generator, or when using a photoacid generator and heating the coating film after light irradiation as needed, the heating is performed at, for example, 60 to 350°C, preferably around 100 to 300°C. The heating time can be selected from a range of 3 seconds or more (for example, 3 seconds to 5 hours), for example, 5 seconds to 2 hours, preferably 20 seconds to 30 minutes, and usually 1 minute to 3 hours (for example, 5 minutes to 2.5 hours).

[0072] Furthermore, when forming patterns or images (for example, when manufacturing printed circuit boards), the coating film formed on the substrate may be pattern-exposed. This pattern exposure may be performed by scanning with a laser beam or by irradiating with light through a photomask. The un-irradiated areas (unexposed parts) generated by such pattern exposure can be developed (or dissolved) with a developer to form a pattern or image. Alkaline aqueous solutions or organic solvents can be used as developing solutions. Examples of alkaline aqueous solutions include aqueous solutions of alkali metal hydroxides such as potassium hydroxide, sodium hydroxide, potassium carbonate, and sodium carbonate; aqueous solutions of quaternary ammonium hydroxides such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, and choline; and aqueous solutions of amines such as ethanolamine, propylamine, and ethylenediamine.

[0073] The aforementioned alkaline developer is generally an aqueous solution of 10% by mass or less, preferably an aqueous solution of 0.1 to 3.0% by mass. Furthermore, alcohols and surfactants can be added to the developer, preferably in amounts of 0.05 to 10 parts by mass per 100 parts by mass of the developer. Among these, a 0.1-2.38% by mass aqueous solution of tetramethylammonium hydroxide is used. It is possible. Furthermore, as the developing solution, general organic solvents can be used, such as acetone, acetonitrile, toluene, dimethylformamide, methanol, ethanol, isopropanol, propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol propyl ether, propylene glycol butyl ether, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, propylene glycol propyl ether acetate, propylene glycol butyl ether acetate, ethyl lactate, cyclohexanone, etc., and one or more of these can be used as a mixture. Propylene glycol methyl ether, propylene glycol methyl ether acetate, ethyl lactate, etc., are particularly preferred.

[0074] In the present invention, adhesion promoters can be added to improve adhesion to the substrate after development. These adhesion promoters include chlorosilanes such as trimethylchlorosilane, dimethylvinylchlorosilane, methyldiphenylchlorosilane, and chloromethyldimethylchlorosilane; alkoxysilanes such as trimethylmethoxysilane, dimethyldiethoxysilane, methyldimethoxysilane, dimethylvinylethoxysilane, diphenyldimethoxysilane, and phenyltriethoxysilane; silazanes such as hexamethyldisilazane, N,N'-bis(trimethylsilyl)urea, dimethyltrimethylsilylamine, and trimethylsilylimidazole; vinyltrichlorosilane, 3-chloropropyltrimethoxysilane, and 3- Examples of adhesion promoters include silanes such as aminopropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, and 3-(N-piperidinyl)propyltrimethoxysilane; heterocyclic compounds such as benzotriazole, benzimidazole, indazole, imidazole, 2-mercaptobenzimidazole, 2-mercaptobenzothiazole, 2-mercaptobenzoxazole, urazole, thiouracil, mercaptoimidazole, and mercaptopyrimidine; and ureas such as 1,1-dimethylurea and 1,3-dimethylurea, or thiourea compounds. One or more of the above adhesion promoters can be used in combination. The amount of these adhesion promoters added is usually 18% by mass or less, preferably 0.0008 to 9% by mass, and more preferably 0.04 to 9% by mass, in terms of solid content.

[0075] The present invention may include a sensitizer. Examples of usable sensitizers include anthracene, phenothiazene, perylene, thioxanthone, and benzophenonethioxanthone. Furthermore, examples of sensitizing dyes include thiopyrillium salt dyes, merocyanine dyes, quinoline dyes, styrylquinoline dyes, ketocoumarin dyes, thioxanthene dyes, xanthene dyes, oxonol dyes, cyanine dyes, rhodamine dyes, and pyrylium salt dyes. Particularly preferred are anthracene-based sensitizers, which, when used in combination with a cationic curing catalyst (radiosensitive cationic polymerization initiator), dramatically improve sensitivity and also possess radical polymerization initiation capabilities. In the hybrid type of the present invention that uses both the cationic curing system and the radical curing system, the catalyst species can be simplified. Specific anthracene compounds that are effective include dibutoxyanthracene and dipropoxyanthraquinone. The amount of sensitizer added is 0.01 to 20% by mass, preferably 0.01 to 10% by mass, relative to the solid content. The composition of the present invention can be photocured or thermocured using a photoradical generator, a thermal radical generator, a photoacid generator, or a thermal acid generator. When a photoacid generator or thermal acid generator is used, for example, conventional epoxy curing agents (e.g., amines or acid anhydrides) are not used, or if they are used, their content is extremely low, thus improving the storage stability of the composition.

[0076] The above composition was found to be suitable for photocationic polymerization. It has a higher curing rate than other materials (e.g., alicyclic epoxy compounds having an epoxycyclohexyl ring). Due to the fast curing rate, it is possible to reduce the amount of acid generator added, or to use weak acid generators. Reducing the amount of acid generator is important for preventing metal corrosion, as acid-active species may remain even after UV irradiation. The fast curing rate also allows for thick-film curing. Curing by UV irradiation can be applied to materials (equipment) that are sensitive to heat. The thermosetting and photocuring materials using the coating-forming composition of the present invention have characteristics such as low dielectric constant, low dielectric loss tangent, rapid hardening, high transparency, and small curing shrinkage, and can be used for coating and bonding electronic components, optical components (anti-reflective coatings), and precision mechanical components. For example, they can be used for bonding optical elements such as lenses in mobile phones and cameras, light-emitting diodes (LEDs), and semiconductor lasers (LDs), liquid crystal panels, biochips, camera lenses and prisms, magnetic components in hard disks of personal computers, pickups in CD and DVD players (the part that captures light information reflected from the disc), speaker cones and coils, motor magnets, circuit boards, electronic components, and internal engine components of automobiles.

[0077] For hard coat materials used for surface protection of automobile bodies, lamps and electrical appliances, building materials, and plastics, it can be applied to, for example, automobile and motorcycle bodies, headlight lenses and mirrors, plastic lenses for eyeglasses, mobile phones, game consoles, optical films, ID cards, etc. For ink materials used to print on metals such as aluminum and plastics, applications include inks for printing on cards such as credit cards and membership cards, switches and keyboards in electrical appliances and office equipment, and inkjet printer inks for CDs, DVDs, etc. Examples of applications include the creation of complex three-dimensional objects by curing resin in combination with 3D CAD, applications to stereolithography for the production of industrial product models, and applications to optical fiber coating, bonding, optical waveguides, and thick film resists.

[0078] Furthermore, the film-forming composition of the present invention can be suitably used as an insulating resin for electronic materials such as anti-reflective films, semiconductor encapsulating materials, adhesives for electronic materials, printed circuit board materials, interlayer insulating film materials, buffer coating agents for semiconductors, enamel insulating materials, and encapsulating materials for power modules, as well as an insulating resin used in high-voltage equipment such as generator coils, transformer coils, and gas-insulated switchgear. The hollow silica sol of the present invention can be manufactured by the following steps (I) to (II). (I) Step: Step to prepare hollow silica sol, (II) Step: Add monovalent alkali metal ions to the hollow silica sol from step (I) in a molar ratio of 7.12 × 10¹⁶ to the SiO2 of the hollow silica particles, converted to M₂O (where M represents a monovalent alkali metal atom). -6 ~285×10 -6 A hollow silica sol can be obtained by adjusting the ratio to the specified proportion. In step (II) above, it is preferable to use a sodium ion as the monovalent alkali metal ion. In step (II) above, the sodium ion content can be adjusted by contacting the hollow silica sol obtained in step (I) with a cation exchange resin, or by adding a sodium source. In step (II) above, the sodium source added is sodium hydroxide, and it is preferable to add it as an aqueous sodium hydroxide solution. The dispersion medium in steps (I) and (II) can be water, alcohols having 1 to 10 carbon atoms, ketones, ethers, amides, ureas, or esters. Examples of these dispersion media include the solvents mentioned above.

[0079] In the present invention, at least one step selected from (i) to (iv) below can be added to the above steps (I), (II), or both. (i): Adding an amine to a hollow silica sol. (ii) Add sodium aluminate as an aluminum source and heat to form aluminosilicate sites in hollow silica particles. (iii): Replacing the dispersion medium with another dispersion medium. (iv): The hollow silica particles are further coated with at least one silane compound selected from the group represented by formulas (1) and (2). Furthermore, in this invention, a hollow silica sol having a dynamic light scattering particle diameter value that is increased compared to the dynamic light scattering particle diameter at the time of manufacture is used, and monovalent alkali metal ions are added to the SiO2 of the hollow silica particles in the hollow silica sol in a molar ratio converted to M2O (where M represents a monovalent alkali metal atom) of 7.12 × 10⁻¹⁶. -6 ~285×10 -6By adding a certain proportion, a method for stabilizing hollow silica sols containing hollow silica particles with internal space in their outer shells can be provided, thereby reducing the increased dynamic light scattering particle size. In the above stabilization method, monovalent alkali metal ions can be sodium ions.

[0080] (ii) The hollow silica sol in step (ii) is prepared by adding 0.0001 to 0.5 g of aluminum compound per gram of hollow silica particles to an aqueous sol and heating it at 40 to 260°C for 0.1 to 24 hours. The amount of aluminum compound added per gram of hollow silica particles in step (ii) can be in the range of 0.0001 to 0.5 g, 0.001 to 0.1 g, or 0.001 to 0.05 g. The heating temperature in step (ii) is 40 to 260°C, 50 to 260°C, or 60 to 240°C, but for non-hydrothermal treatment, it can be 40 to less than 100°C, 50 to less than 100°C, or 60 to less than 100°C, and for hydrothermal treatment, it can be 100 to 260°C or 150 to 240°C. (ii) The heating time in the process can be in the range of 0.1 to 48 hours, or 0.1 to 24 hours, or 0.1 to 10 hours, or 1 to 10 hours.

[0081] (I) The hollow silica particles used in the process have a silica outer shell with a space inside the outer shell. Hollow silica is obtained by forming a silica-based outer shell on the surface of a core-like portion called a template in an aqueous dispersion medium, and then removing the core-like portion. The template can be made using either an organic material (e.g., hydrophilic organic resin particles such as polyethylene glycol, polystyrene, or polyester) or an inorganic material (e.g., hydrophilic inorganic compound particles such as calcium carbonate or sodium aluminate). (I) The hollow silica aqueous sol used as a raw material in step (I) can be a non-hydrothermal treated hollow silica aqueous sol that has been heated in an aqueous medium at a temperature of less than 100°C, for example, between 20 and 100°C, between 40 and 100°C, or between 50 and 100°C. Furthermore, the hollow silica aqueous sol used in step (I) can be a hollow silica aqueous sol that has undergone hydrothermal treatment in an aqueous medium at a heating temperature of 100°C to 240°C, or 110°C to 240°C.

[0082] The hollow silica sol used as a raw material in this invention can be a non-hydrothermally treated hollow silica aqueous sol, a hydrothermally treated hollow silica aqueous sol, or a mixture thereof. This forms aluminosilicate sites on the outer shell of the hollow silica particles, and since aluminosilicate sites may hold alkali metals, the hollow silica sol used as a raw material can be selected so that the aluminum atoms measured by the leaching method are bonded to the surface of the hollow silica particles at a rate of 100 to 20,000 ppm / SiO2 relative to the mass of SiO2 in the hollow silica particles, in terms of Al2O3. (ii) In step (ii), an aluminum compound is added to the hollow silica aqueous sol. The aluminum compound can be added to the hollow silica aqueous sol in solid or aqueous solution form. (ii) The aluminum compound used in step (ii) is at least one aluminum compound selected from the group consisting of aluminates, aluminum alkoxides, and their hydrolysates, and can be used as an aqueous solution containing them. Examples of aluminates include sodium aluminate, potassium aluminate, calcium aluminate, magnesium aluminate, ammonium aluminate, and aluminate amine salts. Examples of oxides include aluminum isopropoxide and aluminum butoxide. Aluminates, in particular, can be used with preference.

[0083] These aluminum compounds are added in aqueous solution form to the hollow silica aqueous sol obtained in step (I), with the concentration of the aqueous solution of the aluminum compounds being used in the range of 0.01 to 20% by mass, 0.1 to 10% by mass, or 0.5 to 5% by mass. The addition can be carried out under stirring of the hollow silica aqueous sol obtained in step (I). The addition time can be completed before heating, or it can be carried out throughout the entire heating time. The impregnation of the hollow silica particles with the desired amount of aluminum compound depends on the processing temperature in step (ii), and therefore, heat treatment must be performed within the above temperature range. (i) The step may further include the addition of an amine. The amine can be any of the above-mentioned amines and can be contained in the hollow silica sol within the above range.

[0084] Step (ii) above may include a step of heating the aluminum compound, or the aluminum compound with at least one additive consisting of an amine and a neutral salt, followed by contact with a cation exchange resin, a step of adding an acid, or a combination thereof. The cation exchange resin is an H-type strongly acidic cation exchange resin, and it may also be subsequently contacted with an anion exchange resin. The acid may be an inorganic acid such as sulfuric acid, nitric acid, hydrochloric acid, or phosphoric acid, or an organic acid such as citric acid, acetic acid, malic acid, lactic acid, succinic acid, tartaric acid, butyric acid, fumaric acid, propionic acid, or formic acid. In the present invention, step (ii) above can be a step in which the aluminum compound (e.g., sodium aluminate) is added and heat-treated at 100 to 240°C for 0.1 to 48 hours, after which an acid (e.g., sulfuric acid, nitric acid, hydrochloric acid) is added and brought into contact with a cation exchange resin. The addition of the acid is a leaching operation that dissolves aluminum-containing components that were not doped into the particles by the heat treatment, as well as metal impurities contained in the particles, into the liquid, and these metal-containing components are removed with the cation exchange resin. Furthermore, after heating and aging at 40 to 100°C for 0.1 to 48 hours, the mixture can be brought into contact with the cation exchange resin again.

[0085] (iii) As a further step, the aqueous medium of the hollow silica aqueous sol is replaced with an alcohol, ketone, ether, or ester having 1 to 10 carbon atoms. Furthermore, the process may include step (iv), in which at least one silane compound selected from the group consisting of formulas (1) and (2) above is added and heated. Steps (iii) and (iv) above may be steps in which, after the completion of step (ii), the solvent is replaced with an alcohol having 1 to 10 carbon atoms in step (iii), and then at least one silane compound selected from the group consisting of formulas (1) and (2) is added in step (iv), heated, and then the solvent is further replaced with a ketone, ether, amide, urea, or ester having 1 to 10 carbon atoms. By using the above method for producing hollow silica sol, the surface charge of the hollow silica particles contained in the sol can be adjusted. [Examples]

[0086] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. The hollow silica sols used in the examples and comparative examples are as follows:

[0087] [Hollow silica sol] Aqueous dispersion of hollow silica sol (manufactured by Ningbo Dilato, product name: HKT-A20-40D, hollow silica aqueous sol heated in an aqueous medium at temperatures between 100°C and 240°C, pH 9.3, dynamic light scattering particle size 55 nm, average primary particle size observed by TEM: 43 nm, TEM-equivalent specific surface area (D) 63 m²). 2 / g, specific surface area ratio (C / D ratio) is 2.4, The lichen concentration is 20% by mass, and the amount of Na contained is 14 ppm / SiO2, meaning the amount of Na2O contained is 6.64 × 10⁻¹⁰, expressed as a molar ratio of Na2O to SiO2. -6 moles / SiO2)

[0088] [Basic compounds] Sodium hydroxide aqueous solution (Kanto Chemical Co., Ltd., product name: 4 mol / L sodium hydroxide solution) Diethanolamine (Tokyo Chemical Industries, Ltd., product name: Diethanolamine) The physical properties of the aqueous-dispersed hollow silica sol, the dispersion of silica particles prepared in the examples and comparative examples, and the hollow silica sol and dispersion during the manufacturing process of the dispersion were measured and evaluated according to the following method.

[0089] [Measurement of silica (SiO2) concentration] The silica concentration of aqueous-dispersed hollow silica sol, methanol-dispersed hollow silica sol, hollow silica sol used in the manufacturing process of the methanol-dispersed hollow silica sol, and dispersions of surface-modified silica particles was calculated by placing these hollow silica sols or dispersions in a crucible, removing the solvent by heating, calcining at 1000°C, and weighing the calcined residue.

[0090] [Measuring pH] The pH was measured at 25°C using a pH meter (manufactured by Toa DKK Co., Ltd., product name: MM-43X). For organic solvents that can be arbitrarily mixed with water, such as methanol sol and propylene glycol monomethyl ether sol, measurements were taken using a solution prepared by mixing the sol with pure water in a mass ratio of 1:1. For organic solvent sols with low solubility in water, such as methyl ethyl ketone sol, measurements were taken using a solution prepared by mixing pure water with methanol and its organic solvent sol in a mass ratio of 1:1:1.

[0091] [Moisture measurement] The water content of the organic solvent dispersion sol was measured by Karl Fischer titration.

[0092] [Analysis method for sodium content] 0.2 g of powder obtained by drying hollow silica sol was treated with 20 mL of a 48% by mass hydrofluoric acid solution to remove the silica component, and the residue was dissolved in 20 mL of a 0.1 mol / liter (N / 10) nitric acid aqueous solution. The Na content in the resulting aqueous solution was measured using an ICP-OES analyzer (product name CIROS120 E0P, manufactured by Rigaku Corporation), and the Na content in the total silica particles was determined by dividing the result by the Si content.

[0093] [Dynamic Light Scattering (DLS) Particle Size Measurement] Particle size was measured using a dynamic light scattering particle size analyzer (Spectris, Inc., product name: Zetasizer Nano). The Z-average particle size was used as the dynamic light scattering particle size.

[0094] [Specific surface area (C) (S) of nitrogen adsorption method (BET method) N2 ) measurement] Specific surface area (S) of silica particles by nitrogen adsorption method in aqueous dispersion hollow silica sol N2 In this method, water-soluble cations in a water-dispersed hollow silica sol were removed using a cation exchange resin (Dow Chemical Company, product name: Amberlite IR-120B), and the hollow silica sol was dried at 290°C to prepare the sample for measurement. This sample was then measured using a nitrogen adsorption specific surface area analyzer, Monosorb (Quantachrome Instruments Japan LLC).

[0095] [Measurement of average primary particle diameter using TEM (transmission electron microscope)] Silica particles in hollow silica sol were photographed using a transmission electron microscope (JEOL Ltd., product name: JEM-F200), and an automated image processing and analysis system (Nireco Corporation, product name: LU) was used. At ZEX' AP, approximately 300 arbitrarily selected particles were binarized, and the diameter obtained by converting the projected area to a circular shape was measured as the average primary particle diameter (HEYWOOD diameter).

[0096] [TEM conversion specific surface area (D)] True density 2.2g / cm 3 Assuming the particles are perfectly spherical, the average primary particle diameter obtained by [measurement of average primary particle diameter by TEM (transmission electron microscope)] was used to calculate the (TEM-equivalent specific surface area (D) = 2720 / average primary particle diameter).

[0097] [Measurement of the amount of aluminum (A) bonded to the surface of hollow silica particles / leaching method] The cation components in the hollow silica sol were removed with an H-type cation exchange resin, and the solvent was removed by heat treatment. The dried material was then pulverized in a mortar and pestle and further treated at 250°C for 2 hours. 0.2 g of the obtained powder was placed in a polypropylene container (PP sample bottle, 50 mL) containing 20 mL of 0.1 mol / liter (N / 10) nitric acid aqueous solution and vigorously shaken by hand. Next, ultrasonic treatment was performed for 10 minutes using an ultrasonic cleaner (AS ONE ASU CLEANER ASU-10M) to thoroughly mix the powder with the nitric acid aqueous solution. This was then placed in a 50°C constant temperature bath and held for 17 hours. Subsequently, the internal solution was cooled to room temperature, loaded into a centrifugal ultrafiltration filter (Amicon Ultra-15, molecular weight cutoff of 10,000), and centrifuged. The amount of aluminum in the resulting filtrate was measured using an ICP emission spectrometer, and the amount of aluminum bonded to the surface of the hollow silica particles was calculated as the ratio of the mass of SiO2 in the hollow silica (Al2O3(ppm) / SiO2) in terms of Al2O3.

[0098] [Measurement / Dissolution Method of the Amount of Aluminum (B) Present in the Entire Hollow Silica Particle] 0.2 g of powder obtained by drying accurately weighed hollow silica sol was treated with 20 mL of 48% by mass hydrofluoric acid solution to remove the silica component, and the residue was dissolved in 20 mL of 0.1 mol / liter (N / 10) nitric acid aqueous solution. The amount of aluminum in the resulting aqueous solution was measured using an ICP emission spectrometer, and the amount of aluminum present in the entire hollow silica particles was calculated as the ratio of the mass of SiO2 in the hollow silica (Al2O3 (ppm) / SiO2) in terms of Al2O3.

[0099] [Measurement of surface charge of hollow silica particles] Hollow silica sol was added to and diluted in 10 mL of methanol to achieve a silica concentration of 0.5% by mass, and this was used as the measurement sample. Using a particle charge meter (Voyt Turbo Co., Ltd., product name PCD-06), a 0.001 mol / liter (N / 1000) diallyldimethylammonium chloride solution (Voyt Turbo Co., Ltd.) was used as the cation standard titrator, and the titration value was measured until the flow potential of the measurement sample became zero. The obtained titration value was divided by the amount of silica contained in the measurement sample to convert it to a value per gram of hollow silica particles, and this value was taken as the surface charge (μeq / g-SiO2).

[0100] [Example 1] (a) Step: 150g of aqueous dispersion hollow silica sol (manufactured by Ningbo Dilato, product name: HKT-A20-40D) is placed in a 500cc round-bottom flask and stirred with a magnetic stirrer until the sodium content in the aqueous dispersion hollow silica sol is 384 ppm / SiO2 (i.e., the amount of Na2O contained is 182.16 × 10 as the molar ratio of Na2O to SiO2). -6 A sodium hydroxide aqueous solution was added dropwise to a molar-to-SiO2 ratio. The resulting silica sol had a pH of 10.1, a particle size of 55 nm by dynamic light scattering, an average primary particle size of 43 nm by TEM observation, a silica concentration of 20% by mass, and a specific surface area (C) of 150 m² by BET method. 2 / g, TEM conversion specific surface area (D) 63m 2 The specific surface area ratio (C / D ratio) is 2.4, the amount of aluminum bonded to the particle surface (A) is 0.1 ppm relative to the mass of SiO2 in the hollow silica particles in terms of Al2O3, the amount of aluminum present throughout the particles (B) is 0.5 ppm relative to the mass of SiO2 in the hollow silica particles in terms of Al2O3, (A / B ratio) is 0.20, the amount of sodium contained in the aqueous dispersed hollow silica sol is 384 ppm / SiO2, i.e., the amount of Na2O The quantity is 182 × 10⁻¹⁰, expressed as the molar ratio of Na₂O to SiO₂. -6 The value was moles / SiO2. (b) Step: Subsequently, 56 g of methanol was added to 150 g of the obtained aqueous dispersion hollow silica sol, and water was removed by distillation using a rotary evaporator under heated and reduced pressure (bath temperature: 120°C, pressure: 580 Torr) while feeding methanol, thereby obtaining a methanol dispersion of hollow silica (methanol-dispersed hollow silica sol). When the water content of the methanol-dispersed hollow silica sol became 2.0% by mass or less, the methanol substitution was terminated, and 150 g of methanol-dispersed hollow silica sol was obtained. The obtained methanol-dispersed hollow silica sol had a silica concentration of 21% by mass, a water content of 1.3% by mass, a particle size of 66 nm by dynamic light scattering, a pH of 9.0, and a specific surface area (C) of 150 m² by BET method. 2 / g, TEM conversion specific surface area (D) 63m 2 The specific surface area ratio (C / D ratio) is 2.4, the amount of aluminum bonded to the particle surface (A) is 0.1 ppm relative to the mass of SiO2 in the hollow silica particles in terms of Al2O3, the amount of aluminum present throughout the particles (B) is 0.5 ppm relative to the mass of SiO2 in the hollow silica particles in terms of Al2O3, the (A / B ratio) is 0.20, the amount of sodium contained in the methanol-dispersed hollow silica sol is 384 ppm / SiO2, i.e., the amount of Na2O contained is 182 × 10⁻¹⁰ as the molar ratio of Na2O to SiO2. -6 The value was moles / SiO2. The obtained methanol-dispersed hollow silica sol was sealed in a 30cc glass bottle and stored for 48 hours in an explosion-proof constant temperature bath (manufactured by ESPEC Corporation, product name: constant temperature bath with safety door) at 50°C. The stability of the methanol-dispersed hollow silica sol was confirmed by comparing the dynamic light scattering particle size before and after storage at 50°C. The dynamic light scattering particle size before 50°C exposure was evaluated as "stable" if the value of the dynamic light scattering particle size after 48 hours of storage at 50°C was within 2.0 times the value before storage, and as "unstable" if it exceeded 2.0 times. The stability of the methanol-dispersed hollow silica sol obtained in Example 1 is shown in Table 1.

[0101] [Example 2] (a) Step: 150g of aqueous dispersion hollow silica sol (manufactured by Ningbo Dilato, product name: HKT-A20-40D) is placed in a 500cc round-bottom flask and stirred with a magnetic stirrer until the sodium content in the aqueous dispersion hollow silica sol is 384 ppm / SiO2 (i.e., the amount of Na2O contained is 182.16 × 10 as the molar ratio of Na2O to SiO2). -6 A sodium hydroxide aqueous solution was added dropwise to a molar-to-SiO2 ratio. Then, 0.16 g of diethanolamine was added dropwise while stirring with a magnetic stirrer. The resulting silica sol had a pH of 10.2, a particle size of 55 nm by dynamic light scattering, an average primary particle size of 43 nm by TEM observation, a silica concentration of 20% by mass, and a specific surface area (C) of 150 m² by BET method. 2 / g, TEM conversion specific surface area (D) 63m 2 The values ​​are as follows: / g, specific surface area ratio (C / D ratio) is 2.4, amount of aluminum bonded to the particle surface (A) is 0.1 ppm relative to the mass of SiO2 in the hollow silica particles in terms of Al2O3, amount of aluminum present throughout the particles (B) is 0.5 ppm relative to the mass of SiO2 in the hollow silica particles in terms of Al2O3, (A / B ratio) is 0.20, sodium content in the aqueous dispersed hollow silica sol is 384 ppm / SiO2, i.e., the amount of Na2O contained is 182 × 10 as the molar ratio of Na2O to SiO2. -6 The value was moles / SiO2. (b) Step: Subsequently, 56 g of methanol was added to 150 g of the obtained aqueous dispersion hollow silica sol, and water was removed by distillation using a rotary evaporator under heated and reduced pressure (bath temperature: 120°C, pressure: 580 Torr) while feeding methanol, thereby obtaining a methanol dispersion of hollow silica (methanol-dispersed hollow silica sol). When the water content of the methanol-dispersed hollow silica sol became 2.0% by mass or less, the methanol substitution was terminated, and 150 g of methanol-dispersed hollow silica sol was obtained. The obtained methanol-dispersed hollow silica sol had a silica concentration of 21% by mass, a water content of 0.4% by mass, a particle size of 66 nm by dynamic light scattering, and a specific surface area (C) of 150 m² by BET method. 2 / g, TEM conversion specific surface area (D) 63m 2 / g, specific surface area ratio (C / D ratio) of 2.4, bonded to the particle surface. The amount of aluminum (A) is 0.1 ppm relative to the mass of SiO2 in the hollow silica particles when converted to Al2O3, and the amount of aluminum present in the entire particle (B) is 0.5 ppm relative to the mass of SiO2 in the hollow silica particles when converted to Al2O3, with an (A / B ratio) of 0.20. The amount of sodium contained in the methanol-dispersed hollow silica sol is 384 ppm / SiO2, i.e., the amount of Na2O contained is 182 × 10⁻¹⁰ as the molar ratio of Na2O to SiO2. -6 The value was moles / SiO2. A stability test similar to that in Example 1 was performed and the results are shown in Table 1.

[0102] [Example 3] (a) Step: 150g of aqueous dispersion hollow silica sol (manufactured by Ningbo Dilato, product name: HKT-A20-40D) is placed in a 500cc round-bottom flask and stirred with a magnetic stirrer until the sodium content in the aqueous dispersion hollow silica sol is 384 ppm / SiO2 (i.e., the amount of Na2O contained is 182.16 × 10 as the molar ratio of Na2O to SiO2). -6 A sodium hydroxide aqueous solution was added dropwise to a molar-to-SiO2 ratio. Then, 0.16 g of diethanolamine was added dropwise while stirring with a magnetic stirrer. The resulting silica sol had a pH of 10.2, a particle size of 55 nm by dynamic light scattering, an average primary particle size of 43 nm by TEM observation, a silica concentration of 20% by mass, and a specific surface area (C) of 150 m² by BET method. 2 / g, TEM conversion specific surface area (D) 63m 2 The values ​​are as follows: / g, specific surface area ratio (C / D ratio) is 2.4, amount of aluminum bonded to the particle surface (A) is 0.1 ppm relative to the mass of SiO2 in the hollow silica particles in terms of Al2O3, amount of aluminum present throughout the particles (B) is 0.5 ppm relative to the mass of SiO2 in the hollow silica particles in terms of Al2O3, (A / B ratio) is 0.20, sodium content in the aqueous dispersed hollow silica sol is 384 ppm / SiO2, i.e., the amount of Na2O contained is 182 × 10 as the molar ratio of Na2O to SiO2. -6 The value was moles / SiO2. (b) Step: Subsequently, 56 g of methanol was added to 150 g of the obtained aqueous dispersion of hollow silica sol, and using a rotary evaporator, under heating and reduced pressure (bath temperature: 120°C, reduced pressure degree: 580 Torr), while feeding methanol, water was distilled off to obtain a methanol dispersion of hollow silica (methanol-dispersed hollow silica sol). When the water content of the methanol-dispersed hollow silica sol reached 2.0 mass% or less, the methanol substitution was terminated, and 150 g of the methanol-dispersed hollow silica sol was obtained. 30 g of the methanol-dispersed hollow silica sol was charged into a 50 cc eggplant-shaped flask, and 0.33 g of pure water was added while stirring with a magnetic stirrer. The obtained methanol-dispersed hollow silica sol had a silica concentration of 21 mass%, a water content of 1.5 mass%, a dynamic light scattering particle diameter of 66 nm, and a specific surface area (C) determined by the BET method of 150 m 2 / g, a TEM-converted specific surface area (D) of 63 m 2 / g, a specific surface area ratio (C / D ratio) of 2.4, the amount of aluminum (A) bound to the particle surface was 0.1 ppm in terms of Al₂O₃ relative to the mass of SiO₂ in the hollow silica particles, the proportion of the total aluminum content (B) present in the entire particles in terms of Al₂O₃ relative to the mass of SiO₂ in the hollow silica particles was 0.5 ppm, the (A / B ratio) was 0.20, the sodium content in the methanol-dispersed hollow silica sol was 384 ppm / SiO₂, that is, the contained Na₂O content was 182×10 as the molar ratio of Na₂O to SiO₂ -6 mol / SiO₂. The same stability test as in Example 1 was performed, and the results are shown in Table 1.

[0103] [Example 4] (a) Step: 150 g of an aqueous dispersion of hollow silica sol (manufactured by Ningbo Dilato, trade name: HKT-A20-40D) was charged into a 500 cc eggplant-shaped flask, and while stirring with a magnetic stirrer, the sodium content in the aqueous dispersion of hollow silica sol was 192 ppm / SiO₂ (that is, the contained Na₂O content was 91.08×10 as the molar ratio of Na₂O to SiO₂ -6A sodium hydroxide aqueous solution was added dropwise to a molar-to-SiO2 ratio. Then, 0.16 g of diethanolamine was added dropwise while stirring with a magnetic stirrer. The resulting silica sol had a pH of 9.8, a particle size of 55 nm, and was observed using dynamic light scattering with a mean primary TEM. Particle size: 43 nm, silica concentration: 20% by mass, specific surface area (C) by BET method: 150 m² 2 / g, TEM conversion specific surface area (D) 63m 2 The specific surface area ratio (C / D ratio) is 2.4, the amount of aluminum bonded to the particle surface (A) is 0.1 ppm relative to the mass of SiO2 in the hollow silica particles in terms of Al2O3, the amount of aluminum present throughout the particles (B) is 0.5 ppm relative to the mass of SiO2 in the hollow silica particles in terms of Al2O3, the (A / B ratio) is 0.20, the amount of sodium contained in the aqueous dispersed hollow silica sol is 192 ppm / SiO2, i.e., the amount of Na2O contained is 91 × 10 as the molar ratio of Na2O to SiO2. -6 The value was moles / SiO2. (b) Step: Subsequently, 56 g of methanol was added to 150 g of the obtained aqueous dispersion hollow silica sol, and water was removed by distillation using a rotary evaporator under heated and reduced pressure (bath temperature: 120°C, pressure: 580 Torr) while feeding methanol, thereby obtaining a methanol dispersion of hollow silica (methanol-dispersed hollow silica sol). When the water content of the methanol-dispersed hollow silica sol became 2.0% by mass or less, the methanol substitution was terminated, and 150 g of methanol-dispersed hollow silica sol was obtained. The obtained methanol-dispersed hollow silica sol had a silica concentration of 21% by mass, a water content of 0.6% by mass, a particle size of 66 nm by dynamic light scattering, and a specific surface area (C) of 150 m² by BET method. 2 / g, TEM conversion specific surface area (D) 63m 2 / g, the specific surface area ratio (C / D ratio) is 2.4, the amount of aluminum (A) bound to the particle surface is 0.1 ppm relative to the mass of SiO₂ in the hollow silica particles in terms of Al₂O₃, the ratio of the total aluminum (B) present in the entire particle relative to the mass of SiO₂ in the hollow silica particles in terms of Al₂O₃ is 0.5 ppm, the (A / B ratio) is 0.20, the sodium content in the methanol-dispersed hollow silica sol is 192 ppm / SiO₂, that is, the Na₂O content is 182×10 in terms of the molar ratio of Na₂O to SiO₂ -6 mol / SiO₂. The same stability test as in Example 1 was performed, and the results are shown in Table 1.

[0104] [Example 5] Step (a): 150 g of water-dispersed hollow silica sol (manufactured by Ningbo Dilato, trade name: HKT-A20-40D) was charged into a 500 cc eggplant-shaped flask, and while stirring with a magnetic stirrer, the sodium content in the water-dispersed hollow silica sol was 192 ppm / SiO₂ (that is, the Na₂O content was 91.08×10 in terms of the molar ratio of Na₂O to SiO₂ -6 mol / SiO₂), an aqueous sodium hydroxide solution was added dropwise. Further, while stirring with a magnetic stirrer, 0.16 g of diethanolamine was added dropwise. The obtained silica sol had a pH of 9.8, a dynamic light scattering particle size of 55 nm, an average primary particle size by TEM observation of 43 nm, a silica concentration of 20 mass%, and a specific surface area (C) by the BET method of 150 m 2 / g, the TEM-converted specific surface area (D) is 63 m 2 / g, the specific surface area ratio (C / D ratio) is 2.4, the amount of aluminum (A) bound to the particle surface is 0.1 ppm relative to the mass of SiO₂ in the hollow silica particles in terms of Al₂O₃, the ratio of the total aluminum (B) present in the entire particle relative to the mass of SiO₂ in the hollow silica particles in terms of Al₂O₃ is 0.5 ppm, the (A / B ratio) is 0.20, the sodium content in the water-dispersed hollow silica sol is 192 ppm / SiO₂, that is, the Na₂O content is 91×10 in terms of the molar ratio of Na₂O to SiO₂ -6 mol / SiO₂. (b) Step: Subsequently, 56 g of methanol was added to 150 g of the obtained aqueous dispersion hollow silica sol, and water was removed by distillation using a rotary evaporator under heated and reduced pressure (bath temperature: 120°C, pressure: 580 Torr) while feeding methanol, thereby obtaining a methanol dispersion of hollow silica (methanol-dispersed hollow silica sol). When the water content of the methanol-dispersed hollow silica sol became 2.0% by mass or less, the methanol substitution was terminated, and 150 g of methanol-dispersed hollow silica sol was obtained. 30 g of the obtained methanol-dispersed hollow silica sol was placed in a 50 cc round-bottom flask, and 0.27 g of pure water was added while stirring with a magnetic stirrer. The obtained methanol-dispersed hollow silica sol had a silica concentration of 21% by mass, a water content of 1.5% by mass, and was analyzed using dynamic light scattering particles. Diameter 66 nm, specific surface area (C) 150 m² by BET method. 2 / g, TEM conversion specific surface area (D) 63m 2 The specific surface area ratio (C / D ratio) is 2.4, the amount of aluminum bonded to the particle surface (A) is 0.1 ppm relative to the mass of SiO2 in the hollow silica particles in terms of Al2O3, the amount of aluminum present throughout the particles (B) is 0.5 ppm relative to the mass of SiO2 in the hollow silica particles in terms of Al2O3, the (A / B ratio) is 0.20, the amount of sodium contained in the methanol-dispersed hollow silica sol is 192 ppm / SiO2, i.e., the amount of Na2O contained is 182 × 10 as the molar ratio of Na2O to SiO2. -6 The value was moles / SiO2. A stability test similar to that in Example 1 was performed and the results are shown in Table 1.

[0105] [Example 6] (a) Step: 150 g of aqueous dispersion hollow silica sol (manufactured by Ningbo Dilato, product name: HKT-A20-40D) was placed in a 500 cc round-bottom flask, and 0.16 g of diethanolamine was added dropwise while stirring with a magnetic stirrer. The resulting silica sol had a pH of 9.5, a particle size of 55 nm by dynamic light scattering, an average primary particle size of 43 nm by TEM observation, a silica concentration of 20% by mass, and a specific surface area (C) of 150 m² by BET method. 2 / g, TEM conversion specific surface area (D) 63m 2The values ​​are as follows: / g, specific surface area ratio (C / D ratio) is 2.4, amount of aluminum bonded to the particle surface (A) is 0.1 ppm relative to the mass of SiO2 in the hollow silica particles in terms of Al2O3, amount of aluminum present throughout the particles (B) is 0.5 ppm relative to the mass of SiO2 in the hollow silica particles in terms of Al2O3, (A / B ratio) is 0.20, sodium content in the aqueous dispersed hollow silica sol is 14 ppm / SiO2, i.e., the amount of Na2O contained is 6.64 × 10 as the molar ratio of Na2O to SiO2. -6 The value was moles / SiO2. (b) Step: Subsequently, 56 g of methanol was added to 150 g of the obtained aqueous dispersion hollow silica sol, and water was removed by distillation using a rotary evaporator under heated and reduced pressure (bath temperature: 120°C, pressure: 580 Torr) while feeding methanol, thereby obtaining a methanol dispersion of hollow silica (methanol-dispersed hollow silica sol). When the water content of the methanol-dispersed hollow silica sol became 2.0% by mass or less, the methanol substitution was terminated, and 150 g of methanol-dispersed hollow silica sol was obtained. (c) Step: Subsequently, 100 g of the obtained methanol-dispersed hollow silica sol is stirred with a magnetic stirrer, and the amount of sodium contained in the aqueous-dispersed hollow silica sol is 384 ppm / SiO2, i.e., the amount of Na2O contained is 182.16 × 10 as the molar ratio of Na2O to SiO2. -6 A sodium hydroxide aqueous solution diluted with methanol was added dropwise to a molar-SiO2 ratio. The obtained methanol-dispersed hollow silica sol had a silica concentration of 20% by mass, a water content of 1.8% by mass, a particle size of 78 nm by dynamic light scattering, and a specific surface area (C) of 150 m² by BET method. 2 / g, TEM conversion specific surface area (D) 63m 2 The specific surface area ratio (C / D ratio) is 2.4, the amount of aluminum bonded to the particle surface (A) is 0.1 ppm relative to the mass of SiO2 in the hollow silica particles in terms of Al2O3, the amount of aluminum present throughout the particles (B) is 0.5 ppm relative to the mass of SiO2 in the hollow silica particles in terms of Al2O3, the (A / B ratio) is 0.20, the amount of sodium contained in the methanol-dispersed hollow silica sol is 384 ppm / SiO2, i.e., the amount of Na2O contained is 182 × 10⁻¹⁰ as the molar ratio of Na2O to SiO2.-6 The value was moles / SiO2. A stability test similar to that in Example 1 was performed and the results are shown in Table 1.

[0106] [Comparative Example 1] (a) Step: 150 g of aqueous dispersion hollow silica sol (manufactured by Ningbo Dilato, product name: HKT-A20-40D) was placed in a 500 cc pear-shaped flask, and 0.16 g of diethanolamine was added dropwise while stirring with a magnetic stirrer. (b) Step: Subsequently, 56 g of methanol is added to 150 g of the obtained aqueous dispersion hollow silica sol, and the water is removed by distillation using a rotary evaporator under heated and reduced pressure (bath temperature: 120°C, pressure: 580 Torr) while feeding methanol. A tanol dispersion (methanol-dispersed hollow silica sol) was obtained. When the water content of the methanol-dispersed hollow silica sol became 2.0% by mass or less, the methanol substitution was terminated, and 150 g of methanol-dispersed hollow silica sol was obtained. The obtained methanol-dispersed hollow silica sol had a silica concentration of 20% by mass, a water content of 0.8% by mass, and a particle size of 123 nm as determined by dynamic light scattering. The amount of Na2O contained was 6.64 × 10⁻⁶ as the molar ratio of Na2O to SiO2. -6 moles / SiO2) A stability test similar to that in Example 1 was performed and the results are shown in Table 1. [Table 1] Table 1 ------------------------------------------------------------------ DLS particle size (nm) DLS particle size (nm) DLS particle size (nm) Results (Initial) (Before stability testing) (After stability testing) Example 1 66 66 67 Stable Example 2: 66 66 66 Stable Example 3 66 66 67 Stable Example 4 66 66 67 Stable Example 5 66 66 67 Stable Example 6 78 78 73 Stable Comparative Example 1: 105 105 235 Unstable ------------------------------------------------------------------

[0107] The average particle size measured by dynamic light scattering is 20-150 nm, and the molar ratio of monovalent alkali metal ions to SiO2 in hollow silica particles, converted to M2O (where M represents a monovalent alkali metal atom), is 7.12 × 10⁻¹⁰. -6 ~285×10 -6 Examples 1 to 6, which are sols containing the specified proportions, showed high stability, as the particle size measured by dynamic light scattering after storage at 50°C for 48 hours was within 2.0 times the value before storage. On the other hand, even if the average particle size measured by dynamic light scattering is 20-150 nm, the molar ratio of monovalent alkali metal ions to SiO2 in hollow silica particles, converted to M2O (where M represents a monovalent alkali metal atom), is 7.12 × 10⁻¹⁰. -6 Comparative Example 1, a sol containing less than a certain percentage, showed that its stability was low, as the particle size measured by dynamic light scattering after 48 hours of storage at 50°C was more than 2.0 times greater than before storage.

[0108] Furthermore, as shown in Table 1, the average particle size measured by dynamic light scattering is 20-150 nm, and the molar ratio of monovalent alkali metal ions to SiO2 in hollow silica particles, converted to M2O (where M represents a monovalent alkali metal atom), is 7.12 × 10⁻¹⁰. -6 Even in sols containing less than a certain percentage, the molar ratio obtained by adding monovalent alkali metal ions after methanol substitution, when converted to M2O (where M represents a monovalent alkali metal atom) of monovalent alkali metal ions relative to the SiO2 of hollow silica particles, is 7.12 × 10⁻¹⁰. -6 ~285×10 -6 Example 6, a sol containing the specified proportions, showed high stability, as the particle size measured by dynamic light scattering after 48 hours of storage at 50°C remained within 2.0 times the value before storage. [Industrial applicability]

[0109] The present invention relates to aqueous sols and organic solvent sols containing highly stable hollow silica particles, and further to a method for improving the stability of the above sols whose storage stability has deteriorated, and a method for producing the same.

Claims

1. It contains hollow silica particles with a space inside the outer shell and monovalent alkali metal ions. The monovalent alkali metal ion is M 2 The number of moles converted to O (where M represents a monovalent alkali metal atom) is the number of SiO in hollow silica particles. 2 For the number of moles, 6.64 × 10 -6 A hollow silica sol containing a proportion exceeding [a certain value].

2. The hollow silica sol according to claim 1, wherein the monovalent alkali metal ion is a sodium ion.

3. The hollow silica sol according to claim 1, wherein the average particle size measured by dynamic light scattering is 20 to 150 nm.

4. Furthermore, it contains amines, and the amines are SiO2 in hollow silica particles. 2 The hollow silica sol according to claim 1, wherein the amount is 0.001 to 10% by mass.

5. The hollow silica sol according to claim 4, wherein the amine is at least one amine selected from the group consisting of primary amines, secondary amines, and tertiary amines having 1 to 10 carbon atoms.

6. The hollow silica sol according to claim 4, wherein the amine is a water-soluble amine with a water solubility of 80 g / L or more.

7. Furthermore, the hollow silica particles contain aluminum atoms that have formed aluminosilicate sites. The aluminum atoms are bonded to the surface of the hollow silica particles. The mass of the aluminum atom is equal to the SiO of the hollow silica particle. 2 For the mass of Al 2 O 3 This corresponds to a ratio of 100 to 20,000 ppm (A) in terms of conversion. The mass of the aluminum atoms is determined by using an aqueous solution of at least one mineral acid selected from the group consisting of sulfuric acid, nitric acid, and hydrochloric acid, and by including aluminum atoms bonded to the surface of hollow silica particles. This value is measured by the leaching method, which extracts aluminum atoms from the compound. The hollow silica sol according to claim 1.

8. The mass of aluminum atoms present in the entire hollow silica particles described above is, in terms of Al 2 O 3 expressed as a proportion (B) of 120 to 50000 ppm relative to the mass of SiO in the hollow silica particles, and the mass of the aluminum atoms is a value measured by dissolving the hollow silica particles in a hydrofluoric acid aqueous solution using a dissolution method, 2 ​ The hollow silica sol according to claim 7, wherein the above ratio (A) / the above ratio (B) is 0.002 to 1.

0.

9. The hollow silica sol according to claim 1, comprising the hollow silica particles wherein the ratio of [specific surface area of ​​silica particles by the BET method (nitrogen gas adsorption method) (C)] / [specific surface area of ​​silica particles calculated from a transmission electron microscope (D)] is 1.40 to 5.

00.

10. The surface charge amount of the above hollow silica particles is SiO 2 The hollow silica sol according to claim 1, comprising hollow silica particles that, when converted, amount to 5 to 250 μeq / g per gram.

11. The above hollow silica particles are further represented by the following formulas (1) and (2): 【Chemistry 1】 (In formula (1), R 1 These are groups that bond to silicon atoms, and which are independent of each other. This represents an alkyl group, a halogenated alkyl group, an alkenyl group, an aryl group, or an organic group having an epoxy group, (meth)acryloyl group, mercapto group, amino group, ureido group, polyether group, carboxyl group, protected carboxyl group, carboxyl group generating group, imide group, or cyano group, and being bonded to a silicon atom by a Si-C bond, or a combination of these groups. R 2 This refers to a group or atom bonded to a silicon atom, which independently represents an alkoxy group, acyloxy group, hydroxyl group, or halogen atom having one or more carbon atoms, or a combination thereof. a represents an integer between 1 and 3. In formula (2), R 3 This refers to a group that is bonded to a silicon atom and independently represents an alkyl group, a halogenated alkyl group, an alkenyl group, an aryl group, or an organic group having an epoxy group, (meth)acryloyl group, mercapto group, amino group, ureido group, polyether group, carboxyl group, protected carboxyl group, carboxyl group generating group, imide group, or cyano group, and is bonded to a silicon atom by a Si-C bond, or a combination of these groups. R 4 This refers to a group or atom bonded to a silicon atom, which independently represents an alkoxy group, acyloxy group, hydroxyl group, or halogen atom having one or more carbon atoms, or a combination thereof. Y represents a group or atom bonded to a silicon atom, such as an alkylene group, an NH group, or an oxygen atom. b represents an integer between 1 and 3, and c represents an integer of 0 or 1. The hollow silica sol according to claim 1, comprising hollow silica particles coated with at least one silane compound selected from the group consisting of compounds represented by .

12. The hollow silica sol according to claim 1, wherein the dispersion medium for the hollow silica sol is water, an alcohol having 1 to 10 carbon atoms, a ketone, an ether, an amide, a urea, or an ester.

13. A film-forming composition comprising hollow silica particles derived from the hollow silica sol described in any one of claims 1 to 12, and an organic resin or polysiloxane.

14. A film obtained from the film-forming composition according to claim 13, having a visible light transmittance of 80% or more.

15. The following steps (I) to (II): (I) Step: A step of preparing a hollow silica sol containing a dispersion medium. (II) Step: Adding SiO2 of hollow silica particles to the hollow silica sol from step (I). 2 For monovalent alkali metal ions, M 2 The molar ratio converted to O (where M represents a monovalent alkali metal atom) is 6.64 × 10 -6 A step of adding monovalent alkali metal ions to adjust the ratio to exceed the following: A method for producing a hollow silica sol according to any one of claims 1 to 12, including the following:

16. The method for producing a hollow silica sol according to claim 15, wherein the monovalent alkali metal ion in step (II) above is a sodium ion.

17. The method for producing a hollow silica sol according to claim 16, wherein the adjustment of the sodium ion content in step (II) above is to bring the hollow silica sol obtained in step (I) into contact with a cation exchange resin, or to add a sodium source.

18. The method for producing a hollow silica sol according to claim 16, wherein the addition of the sodium source in step (II) above is the addition of sodium hydroxide.

19. The method for producing a hollow silica sol according to claim 15, wherein the dispersion medium in steps (I) and (II) above is water, an alcohol having 1 to 10 carbon atoms, a ketone, an ether, an amide, a urea, or an ester.

20. A method for producing a hollow silica sol according to claim 15, wherein at least one step selected from (i) to (iv) below is added to step (I), step (II), or both steps. (i): Adding an amine to a hollow silica sol, (ii): Adding sodium aluminate as an aluminum source and heating it to form aluminosilicate sites in hollow silica particles. (iii): Replacing one dispersion medium with another dispersion medium. (iv): The hollow silica particles are further coated with at least one silane compound selected from the group consisting of formulas (1) and (2).

21. A method for stabilizing a hollow silica sol containing hollow silica particles having a space inside the outer shell, In hollow silica sols where the average particle size measured by dynamic light scattering has increased compared to the time of manufacture, The above monovalent alkali metal ions are M 2 The number of moles converted to O (where M represents a monovalent alkali metal atom) is the amount of SiO in the hollow silica particles in the hollow silica sol. 2 For the number of moles, 6.64 × 10 -6 Add the monovalent alkali metal ions so that the molar ratio exceeds the following: The method according to claim 1, characterized by reducing the average particle size obtained by the increased dynamic light scattering method. A method for stabilizing hollow silica sol.

22. The method for stabilizing a hollow silica sol according to claim 21, wherein the monovalent alkali metal ion is a sodium ion.

Citation Information

Patent Citations

  • Method for producing silica-based fine particle-dispersed sol, silica-based fine particle-dispersed sol, coating composition containing silica-based fine particle-dispersed sol, curable coating film, and base with curable coating film

    JP2011026183A

  • Silica fine particle, paint for forming coating film and base material with coating film

    JP2011046606A

  • Silica-based fine particles, coating for forming coating film, and base material having coating film formed thereon

    JP2013121911A

  • Ceria-based composite hollow microparticle dispersion, production method thereof, and polishing abrasive grain dispersion comprising ceria-based composite hollow microparticle dispersion

    JP2019127405A

  • Silica particle having mesh-like outline and internal space and method for producing the same

    JP2021024765A